Heat resistant propylene-ethylene copolymers and adhesives containing propylene-ethylene copolymers

CN119301165APending Publication Date: 2025-01-10XINTEMA ADHESIVE TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280093951.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2022-09-01
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

然而,这些蜡是高脆性材料(如由低针头穿透力所指示的),使其熔化会消耗大量能源

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301165A_ABST
    Figure CN119301165A_ABST
Patent Text Reader

Abstract

The present invention provides a category of propylene-ethylene copolymers that have been found to be readily useful in high heat resistance applications and form adhesives with improved mechanical strength and heat resistance. More specifically, these propylene-ethylene copolymers have specific propylene content, triad tacticity, ring and ball softening point, and crystallinity, thereby providing copolymers exhibiting desirable high heat resistance, tensile strength, and elongation. In addition, these propylene-ethylene copolymers can be used to produce adhesives exhibiting excellent heat resistance characteristics and superior cohesive strength.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of priority to the following U.S. Provisional Patent Applications: U.S. Provisional Patent Application Serial No. 63 / 269,737, filed on March 22, 2022, entitled “HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS”; U.S. Provisional Patent Application Serial No. 63 / 269,738, filed on March 22, 2022, entitled “PROCESS FOR MAKING HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS”; U.S. Provisional Patent Application Serial No. 63 / 269,742, filed on March 22, 2022, entitled “COMPOSITIONS COMPRISING HEAT RESISTANT PROPYLENE-ETHYLENE COPOLYMERS”; and U.S. Provisional Patent Application Serial No. 63 / 269,742, filed on March 22, 2022, entitled “PROPYLENE-ETHYLENE COPOLYMER BASED HOT MELT COMPOSITIONS WITH IMPROVED HEAT RESISTANCE" and the entire disclosures of these patent applications are incorporated herein by reference. Background Art

[0003] Hot melt adhesives used in high temperature applications need to have structural integrity and durability at high temperatures as well as below room temperature. Examples are durable assembly applications such as appliances and automotive interior trims positioned above the beltline of a seat. For these demanding applications, polyester, polyamide and moisture-curable polyurethane (PUR) based hot melt reactive adhesives, solvent-based one-component reactive adhesives and water-based polyurethanes (polyurethane dispersions) are often used.

[0004] Vehicle interior parts such as instrument panels and door trims typically contain olefin-based resins such as polypropylene (PP), acrylonitrile-butadiene-styrene copolymers (ABS) and vinyl chloride as base substrates, with PP or urethane foam skin materials, typically fabric or artificial leather coverings, laminated on the surface to provide a good look and feel. Thermoplastic polyolefin compounds (TPOs), such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, have become increasingly popular for automotive interior parts such as, for example, instrument panels, center consoles, door panels, headliners, and interior trims.

[0005] Solvent-based modified chloroprene one-component reactive adhesives can provide excellent heat-resistant creep properties. However, these chemicals can be expensive and harmful to the environment, and there are still some disadvantages when using reactive hot melt adhesives, such as short pot life, narrow application temperature window, difficulty in balancing pot life and curing time, and long curing time may lead to processing difficulties. Additionally, these adhesives typically show poor adhesion to polyolefin substrates. High cost and potential health hazards associated with unreacted monomers in car interiors are prompting OEMs and formulators to look for polyolefin-based hot melt adhesives that can provide high temperature resistance and good adhesion to polyolefin-based substrates and a good application temperature window.

[0006] Adhesives are desired to have an extended open time (working time between the time the adhesive is dispensed and the time when a bond between the substrates can no longer be formed) and good heat resistance, particularly as measured by thermal creep resistance. Vehicle interior trims typically require a practical heat resistance of about 80°C. For example, U.S. Patent Application Publication No. 2020 / 0017731 provides a polyolefin-based adhesive having a thermal creep resistance of 80°C; however, it has been observed that automotive dashboards may have temperatures as high as 90°C or 100°C.

[0007] Hot melt adhesive compositions containing amorphous poly-alpha olefin (i.e. APO, amorphous polyolefin) or APO / isotactic polypropylene (IPP) blends are well known in the art, and have good adhesion to polyolefin substrates in the absence of hazardous monomers. Adhesives based on APO are typically composed of at least one APO and hydrocarbon tackifying resins, optionally with functionalizable wax. However, it is well known that hot melt adhesives based on APO have poor heat resistance and low cohesive strength, which makes them unsuitable for durable assembly applications, such as automotive interior parts. Recent development has shown that improved APO can provide improved performance and is prepared with multiple polymers, tackifying resins, waxes and oils, but still need to have higher heat resistance while balancing the improved mechanical strength and the APO to the adhesion of the desired substrate.

[0008] Amorphous propylene-ethylene copolymers prepared with known Ziegler-Natta catalysts are compositions that can be used in hot melt adhesive applications. Such copolymers can be intermolecularly inhomogeneous in terms of stereoregularity and / or composition. In addition, such copolymers can also be inhomogeneous in composition within the polymer chain. Such characteristics can be but not always the result of the type of reactor process conditions and / or catalyst system used. However, the tensile strength, elongation and thermotolerance of such copolymers are usually not suitable for thermotolerance applications.

[0009] In addition, it is known that when preparing an adhesive compound suitable for heat resistance, a high melting point / softening point polypropylene wax can be added to the composition to improve heat resistance, wherein the PP wax with a melting point of at least 145° C. accounts for up to 14% by weight of the formula. In order to achieve the desired high melting point or softening point, these waxes usually have very high crystallinity. However, these waxes are highly brittle materials (as indicated by low needle penetration), and melting them consumes a lot of energy. Therefore, polypropylene wax with high stereoregularity and melting point / softening point usually has poor compatibility with the main polyolefin polymer of the adhesive, usually has low molecular weight, and shortens the adhesive open time. Due to this incompatibility between the wax and the main polyolefin polymer, the resulting adhesive can show poor cohesive strength, elongation and viscosity.

[0010] Therefore, there remains a need for polyolefin polymers that exhibit desirable heat resistance and controllable processing characteristics for use in adhesive compositions. Additionally, there is a need for polyolefin polymers that can produce adhesives having high heat resistance and high cohesive strength. Summary of the invention

[0011] One or more aspects of the present disclosure generally relate to propylene-ethylene copolymers comprising propylene and ethylene. In addition, the propylene-ethylene copolymer: (a) comprises 89 wt% to 98 wt% propylene, (b) has a Ring and Ball softening point of at least 135°C, (c) has a triad tacticity (mm%) of at least 50%, and (d) has a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g.

[0012] With respect to the propylene-ethylene copolymer disclosed above, one or more aspects of the present disclosure generally relate to an adhesive comprising the propylene-ethylene copolymer mentioned above. As described above, the propylene-ethylene copolymer: (a) comprises 89 wt% to 98 wt% propylene, (b) has a Ring and Ball softening point of at least 135°C, (c) has a triad tacticity (mm%) of at least 50%, and (d) has a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g. In addition, the adhesive comprises: (a) 5 wt% to 100 wt% of the propylene-ethylene copolymer; (b) 0 wt% to 90 wt% of at least one second polymer; (c) no more than 70 wt% of at least one tackifier; (d) no more than 20 wt% of a processing oil; and (e) no more than 35 wt% of at least one wax.

[0013] The following statements relate to various aspects of the present disclosure. The following statements about these aspects may be combined in any combination or may be applied separately to the associated aspects (e.g., one of the following limitations may apply to the first aspect, while another limitation may not apply to the first aspect).

[0014] According to a first aspect of the present disclosure, there is provided a propylene-ethylene copolymer comprising propylene and ethylene, wherein the propylene-ethylene copolymer: (a) comprises 89 wt% to 98 wt% propylene, (b) has a Ring and Ball softening point of at least 135°C, (c) has a triad tacticity (mm%) of at least 50%, and (d) has a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g.

[0015] With regard to the first aspect, the propylene-ethylene copolymer may comprise from 0.5 wt% to 11 wt% ethylene.

[0016] Additionally or alternatively, the propylene-ethylene copolymer has a viscosity of 1,000 cP to 50,000 cP at 190°C.

[0017] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 2,000 cP to 7,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 1.5 MPa to 8 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0018] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 7,000 cP to 15,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 3 MPa to 10 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0019] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 15,000 cP to 27,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 3 MPa to 14 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0020] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity greater than 27,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of at least 7 MPa, and (d) a heat of crystallization of 25 J / g to 50 J / g.

[0021] Additionally or alternatively, the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135°C to 160°C.

[0022] Additionally or alternatively, the propylene-ethylene copolymer has a triad tacticity in the range of 50% to 70%.

[0023] Additionally or alternatively, the propylene-ethylene copolymer has a needle penetration force in the range of 0.1 dmm to 21 dmm.

[0024] Additionally or alternatively, the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 MPa to 14 MPa.

[0025] Additionally or alternatively, the propylene-ethylene copolymer has an elongation at break greater than 300%.

[0026] Additionally or alternatively, the propylene-ethylene copolymer has a heat of crystallization (Hc, 20°C / min cooling rate) in the range of 20 J / g to 55 J / g.

[0027] Additionally or alternatively, the propylene-ethylene copolymer: (a) exhibits a needle penetration of 0.1 dmm to 21 dmm, (b) has a heat of crystallization of 25 J / g to 55 J / g, and (c) has one of the following characteristics:

[0028] (i) having a viscosity of 2,000 cP to 7,000 cP at 190°C and exhibiting a tensile strength at break of 1.5 MPa to 8 MPa, or

[0029] (ii) having a viscosity of 7,000 cP to 15,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 8 MPa,

[0030] (iii) having a viscosity of 15,000 cP to 27,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 14 MPa, or

[0031] (iv) having a viscosity greater than 27,000 cP at 190°C, exhibiting a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 J / g to 50 J / g.

[0032] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a triad tacticity in the range of 53% to 78%, (b) exhibits a Ring and Ball softening point of 135°C to 165°C, and (c) exhibits a heat of crystallization of 28 J / g to 60 J / g.

[0033] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 15,000 cP to 50,000 cP at 190°C, (b) exhibits a tensile strength at break of at least 3 MPa, and (c) exhibits an elongation at break of at least 300%.

[0034] According to a second aspect of the present disclosure, there is provided a composition comprising the propylene-ethylene copolymer as discussed in the first aspect, and additives and substitutes related to the first aspect.

[0035] According to a third aspect of the present disclosure, there is provided a process for producing a propylene-ethylene copolymer as discussed in the first aspect in the presence of a Ziegler-Natta catalyst system, as well as additions and alternatives related to the first aspect.

[0036] According to a fourth aspect of the present disclosure, there is provided an adhesive, the adhesive comprising:

[0037] (a) 5 to 100 weight percent of at least one propylene-ethylene copolymer, wherein the propylene-ethylene copolymer comprises ethylene and propylene, wherein the propylene-ethylene copolymer:

[0038] (i) contains from 89 to 98% by weight of propylene,

[0039] (ii) having a Ring and Ball softening point of at least 135°C,

[0040] (iii) having a triad tacticity (mm%) of at least 50%, and

[0041] (iv) having a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g;

[0042] (b) 0% to 90% by weight of at least one second polymer;

[0043] (c) no more than 70% by weight of at least one tackifier;

[0044] (d) not more than 20% by weight of process oil; and

[0045] (e) not more than 35% by weight of at least one wax.

[0046] Regarding the fourth aspect, the adhesive composition includes 5 wt % to 55 wt % of the second polymer.

[0047] Additionally or alternatively, the adhesive composition has (a) a shear adhesion failure temperature of at least 135°C, and / or (b) a thermal creep length at 110°C of 5 mm or less.

[0048] Additionally or alternatively, the adhesive composition has (a) a shear adhesion failure temperature of at least about 135°C, and (b) a thermal creep length at 120°C of 5 mm or less.

[0049] Additionally or alternatively, the adhesive composition comprises: (a) 10 wt% to 70 wt% of a propylene-ethylene copolymer, (b) 5 wt% to 55 wt% of a second polymer, (c) no more than 70 wt% of a tackifier, (d) no more than 20 wt% of a processing oil, and (e) no more than 20 wt% of a wax.

[0050] Additionally or alternatively, the adhesive composition comprises: (a) 5 wt% to 95 wt% of a propylene-ethylene copolymer, (b) 5 wt% to 90 wt% of a second polymer, (c) no more than 70 wt% of a tackifier, (d) no more than 20 wt% of a processing oil, and (e) no more than 20 wt% of a wax.

[0051] Additionally or alternatively, the adhesive composition comprises: (a) 30 wt% to 80 wt% of a propylene-ethylene copolymer, (b) 1 wt% to 45 wt% of a second polymer, (c) no more than 70 wt% of a tackifier, (d) no more than 20 wt% of a process oil, and (e) no more than 20 wt% of at least one wax.

[0052] Additionally or alternatively, the adhesive composition comprises less than 10 wt % wax.

[0053] Additionally or alternatively, the second polymer is at least one polymer selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers, copolymers produced from propylene and linear or branched C4-C10 alpha-olefin monomers, copolymers produced from ethylene and linear or branched C4-C10 Copolymers produced from α-olefin monomers, functionalized polyolefins, isoprene-based block copolymers, butadiene-based block copolymers, hydrogenated block copolymers, styrene-ethylene / butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene / propylene-styrene (SEPS), ethylene vinyl acetate copolymers, polyesters, polyester-based copolymers, chloroprene rubber, urethane, acrylic acid, polyacrylate, acrylate copolymers, polyetheretherketone, polyamide, hydrogenated styrene block copolymers, random styrene copolymers, ethylene-propylene rubber, ethylene vinyl acetate copolymers, butyl rubber, styrene-butadiene rubber, nitrile rubber, natural rubber, polyisoprene, polyisobutylene and polyvinyl acetate.

[0054] Additionally or alternatively, the propylene-ethylene copolymer may comprise from 0.5 wt% to 11 wt% ethylene.

[0055] Additionally or alternatively, the propylene-ethylene copolymer has a viscosity of 1,000 cP to 50,000 cP at 190°C.

[0056] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 2,000 cP to 7,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 1.5 MPa to 8 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0057] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 7,000 cP to 15,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 3 MPa to 10 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0058] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 15,000 cP to 27,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of 3 MPa to 14 MPa, and (d) a heat of crystallization of 25 J / g to 55 J / g.

[0059] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity greater than 27,000 cP at 190°C, (b) exhibits a needle penetration of 0.1 dmm to 21 dmm, (c) exhibits a tensile strength at break of at least 7 MPa, and (d) a heat of crystallization of 25 J / g to 50 J / g.

[0060] Additionally or alternatively, the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135°C to 160°C.

[0061] Additionally or alternatively, the propylene-ethylene copolymer has a triad tacticity in the range of 50% to 70%.

[0062] Additionally or alternatively, the propylene-ethylene copolymer has a needle penetration force in the range of 0.1 dmm to 21 dmm.

[0063] Additionally or alternatively, the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 MPa to 14 MPa.

[0064] Additionally or alternatively, the propylene-ethylene copolymer has an elongation at break greater than 300%.

[0065] Additionally or alternatively, the propylene-ethylene copolymer has a heat of crystallization (Hc, 20°C / min cooling rate) in the range of 20 J / g to 55 J / g.

[0066] Additionally or alternatively, the propylene-ethylene copolymer: (a) exhibits a needle penetration of 0.1 dmm to 21 dmm, (b) has a heat of crystallization of 25 J / g to 55 J / g, and (c) has one of the following characteristics:

[0067] (i) having a viscosity of 2,000 cP to 7,000 cP at 190°C and exhibiting a tensile strength at break of 1.5 MPa to 8 MPa, or

[0068] (ii) having a viscosity of 7,000 cP to 15,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 8 MPa,

[0069] (iii) having a viscosity of 15,000 cP to 27,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 14 MPa, or

[0070] (iv) having a viscosity greater than 27,000 cP at 190°C, exhibiting a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 J / g to 50 J / g.

[0071] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a triad tacticity in the range of 53% to 78%, (b) exhibits a Ring and Ball softening point of 135°C to 165°C, and (c) exhibits a heat of crystallization of 28 J / g to 60 J / g.

[0072] Additionally or alternatively, the propylene-ethylene copolymer: (a) has a viscosity of 15,000 cP to 50,000 cP at 190°C, (b) exhibits a tensile strength at break of at least 3 MPa, and (c) exhibits an elongation at break of at least 300%.

[0073] According to a fifth aspect of the present disclosure, there is provided an article comprising the adhesive composition as discussed in the fourth aspect, and additives and substitutes related to the fourth aspect.

[0074] Regarding the fifth aspect, the article is selected from the group consisting of: adhesives, sealants, caulks, roofing membranes, waterproofing membranes, compounds and pads, carpets, laminates, laminated products, tapes, labels, adhesives, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, modified asphalt, modified asphalt, electronic housings, waterproof membranes, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, glass fiber reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles, motorcycles, motor vehicle molded parts , automotive extrusion parts, clothing articles, rubber additives / processing aids and fibers, wherein the adhesive includes a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile packaging adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible laminating adhesive, a rigid laminating adhesive, a flexible film adhesive, a flexible packaging adhesive, a water-activated adhesive, a home improvement adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a self-adhesive film, a laminating adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive or a sanitary elastic attachment adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Embodiments of the present invention are described herein with reference to the following drawings, in which:

[0076] Figure 1 is a graph comparing the heat of crystallization and softening points of the copolymers and waxes of Tables 3A-3D. DETAILED DESCRIPTION

[0077] We have discovered a class of propylene-ethylene copolymers, which are produced in the presence of a Ziegler-Natta catalyst, that can be readily used in high heat resistance applications and form adhesives with improved mechanical strength and heat resistance. More specifically, we have discovered that propylene-ethylene copolymers with specific propylene content, isotacticity (i.e., triad tacticity), ring and ball softening point, and crystallinity exhibit desired high heat resistance, tensile strength, and elongation. Furthermore, we have discovered that the unique isotacticity of propylene-ethylene copolymers (as demonstrated by triad tacticity) is the key to obtaining desired heat resistance properties and improved mechanical properties.

[0078] These propylene-ethylene copolymers are produced by unique process conditions, more specifically varying the external donor / Ti ratio, varying the ethylene flow rate and adjusting the hydrogen flow rate in the presence of a Ziegler-Natta catalyst.

[0079] In addition, we have found that these propylene-ethylene copolymers of the present invention can be used to produce adhesives that show excellent heat resistance characteristics and superior cohesive strength. More specifically, adhesives comprising propylene-ethylene copolymers of the present invention show improved heat resistance and good peel strength in performance tests, thereby overcoming the shortcomings of the above-mentioned prior art adhesives. Adhesives comprising propylene-ethylene copolymers of the present invention show superior peel strength to substrates of interest and superior thermal creep resistance at high temperatures.

[0080] We have also found that the propylene-ethylene copolymers of the present invention have a unique balance of propylene content, isotacticity (as measured by triad tacticity), and softening point that provides copolymers that can maintain T-peel strength at 90°C and pass thermal creep testing at 110°C in the absence of propylene wax. Additionally, we have found that the propylene-ethylene copolymers of the present invention can tolerate up to 20% by weight of polypropylene wax. Furthermore, it has been found that adhesives containing the propylene-ethylene copolymers of the present invention can be formulated with a combination of 8% to 35% by weight of polyethylene wax and polypropylene wax to adjust the viscosity, fiber tear adhesion, open / set time, and other characteristics of the adhesive.

[0081] Heat-resistant propylene-ethylene copolymer

[0082] In one embodiment or in combination with any embodiment mentioned herein, there is provided a propylene-ethylene copolymer comprising propylene and ethylene; wherein the amount of propylene is in the range of 89 wt% to 98 wt%, wherein the propylene-ethylene copolymer has a Ring and Ball softening point from 135°C to 165°C, a triad tacticity (mm%) of 50% to 75%, and a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g.

[0083] In one embodiment or in combination with any embodiment mentioned herein, there is provided a propylene-ethylene copolymer comprising propylene and ethylene; wherein the amount of propylene is in the range of about 89 wt% to about 98 wt%; wherein the propylene-ethylene copolymer has a Ring and Ball softening point of about 135°C to about 160°C, wherein the propylene-ethylene copolymer has a triad tacticity (mm%) of about 50% to about 70%.

[0084] According to various embodiments, propylene-ethylene copolymer as herein described can comprise different amounts of ethylene.In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise the ethylene of at least 0.5 % by weight, 1 % by weight, 2 % by weight, 3 % by weight, 4 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight or 11 % by weight.Additionally or in the alternative, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise the ethylene that is less than 15 % by weight, 14 % by weight, 13 % by weight, 12 % by weight, 11 % by weight, 10 % by weight, 9 % by weight, 8 % by weight, 7 % by weight, 6 % by weight, 5 % by weight, 4 % by weight or 3 % by weight.

[0085] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can comprise ethylene in the range of about 0.5 wt% to about 11 wt%, about 0.5 wt% to about 10 wt%, about 0.5 wt% to about 9 wt%, about 0.5 wt% to about 8 wt%, about 0.5 wt% to about 7 wt%, about 0.5 wt% to about 6 wt%, about 0.5 wt% to about 5 wt%, about 0.5 wt% to about 4 wt%, or about 0.5 wt% to about 3 wt%, about 1 wt% to about 11 wt%, about 1 wt% to about 10 wt%, about 1 wt% to about 9 wt%, about 1 wt% to about 8 wt%, about 1 wt% to about 7 wt%, about 1 wt% to about 6 wt%, about 1 wt% to about 5 wt%, about 1 wt% to about 4 wt%, or about 1 wt% to about 3 wt%.

[0086] In addition, in various embodiments, propylene-ethylene copolymer can contain different amounts of propylene.In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise at least 89 % by weight, 90 % by weight, 91 % by weight, 92 % by weight, 93 % by weight, 94 % by weight, 95 % by weight, 96 % by weight, 97 % by weight or 98 % by weight propylene.Additionally or in the alternative, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise the propylene that is less than 98 % by weight, 97 % by weight, 96 % by weight, 95 % by weight, 94 % by weight, 93 % by weight or 92 % by weight.

[0087] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can comprise from about 89 wt% to about 97 wt%, from about 89 wt% to about 96 wt%, from about 89 wt% to about 95 wt%, from about 89 wt% to about 94 wt%, from about 89 wt% to about 93 wt%, from about 89 wt% to about 92 wt%, from about 89 wt% to about 91 wt%, from about 90 wt% to about 98 wt%, from about 90 wt% to about 97 wt%, from about 90 wt% to about 96 wt%, from about 90 wt% to about 95 wt%, from about 90 wt% to about 94 wt%, from about 90 wt% to about 93 wt%, from about 90 wt% to about 92 wt%, from about 91 ...1 wt% to about 97 wt%. %, about 91 wt % to about 96 wt %, about 91 wt % to about 95 wt %, about 91 wt % to about 94 wt %, about 91 wt % to about 93 wt %, about 92 wt % to about 98 wt %, about 92 wt % to about 97 wt %, about 92 wt % to about 96 wt %, about 92 wt % to about 95 wt %, about 92 wt % to about 94 wt %, about 93 wt % to about 97 wt %, about 93 wt % to about 96 wt %, about 93 wt % to about 95 wt %, about 94 wt % to about 98 wt %, about 94 wt % to about 97 wt %, about 94 wt % to about 96 wt %, about 95 wt % to about 98 wt %, about 95 wt % to about 97 wt %, or about 96 wt % to about 98 wt % of propylene.

[0088] The ethylene and propylene contents of the copolymers were determined by NMR via the technique described by Wang et al., Macromolecules, 2000, Vol. 33, pp. 1157-1162, the entire contents of which are incorporated herein by reference.

[0089] In one embodiment or in combination with any embodiment mentioned herein, copolymer may contain one or more C4-C10 alpha-olefins. Typically, when used in adhesives, C4-C10 alpha-olefins can be used to increase the resulting bond strength of copolymer. These C4-C10 alpha-olefins may include, for example, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene and combinations thereof. According to one or more embodiments, based on the gross weight of copolymer, copolymer may include no more than 10 wt%, 8 wt%, 5 wt%, 3 wt%, 2 wt%, 1 wt%, 0.5 wt% or 0.1 wt% of at least one C4-C10 alpha-olefin. In addition, in various embodiments, based on the gross weight of copolymer, copolymer may include 0.5 wt% to 10 wt%, 1 wt% to 10 wt%, 2 wt% to 10 wt%, 3 wt% to 10 wt%, 4 wt% to 10 wt% or 5 wt% to 10 wt% of at least one C4-C10 alpha-olefin.

[0090] In certain embodiments, the propylene-ethylene copolymer may not contain any C4-C10 α-olefins.

[0091] Typically, the softening point of the propylene-ethylene copolymer can be changed and optimized by controlling the comonomer content, triad stereoregularity, crystallinity and viscosity of the propylene-ethylene copolymer. It may be desirable that the copolymer has a lower softening point so that the copolymer can be used and processed at a lower application temperature. In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may exhibit a ring and ball softening point of at least 135°C, 140°C or 145°C, as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerol according to ASTM E28 Standard Test Method for Softening Point of Resins Derived from Rosin Chemicals and Hydrocarbons. Additionally or in the alternative, the propylene-ethylene copolymer may exhibit a ring and ball softening point of less than 165°C, 163°C, 160°C, 158°C, 155°C, 153°C, 150°C, 147°C, 145°C, or 140°C as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerin in accordance with ASTM E28 Standard Test Method for Softening Point of Resins Derived from Rosin Chemicals and Hydrocarbons.

[0092] In one embodiment or in combination with any of the embodiments mentioned herein, the copolymer may have a temperature of about 135°C to about 165°C, about 135°C to about 163°C, about 135°C to about 160°C, about 135°C to about 158°C, about 135°C to about 155°C, about 135°C to about 153°C, about 135°C to about 150°C, about 135°C to about 147°C, about 135°C to about 145°C, about 135°C to about 140°C, A ring and ball softening point in the range of about 140°C to about 165°C, about 140°C to about 163°C, about 140°C to about 160°C, about 140°C to about 158°C, about 140°C to about 155°C, about 140°C to about 153°C, about 140°C to about 150°C, about 140°C to about 148°C, about 140°C to about 145°C, about 145°C to about 155°C, or about 145°C to about 150°C, as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerin or silicone oil in accordance with ASTM E28 Standard Test Method for Softening Point of Resins Derived from Rosin Chemicals and Hydrocarbons.

[0093] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a triad tacticity of at least 50 mm content %, 51 mm content %, 52 mm content %, 53 mm content %, 54 mm content %, 55 mm content %, 56 mm content %, 57 mm content %, 58 mm content %, 59 mm content %, 60 mm content %, 61 mm content %, 62 mm content %, 63 mm content %, 64 mm content %, or 65 mm content %. Additionally or in the alternative, the propylene-ethylene copolymer may have a triad tacticity of less than 78 mm content %, 77 mm content %, 76 mm content %, 75 mm content %, 74 mm content %, 73 mm content %, 72 mm content %, 71 mm content %, or 70 mm content %, 69 mm content %, 68 mm content %, 67 mm content %, 66 mm content %, 65 mm content %, 64 mm content %, 63 mm content %, 62 mm content %, 61 mm content %, or 60 mm content %.

[0094] In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may have a triad tacticity in the range of about 50 mm content % to about 78 mm content %, about 53 mm content % to about 78 mm content %, or about 50 mm content % to about 70 mm content %. Other ranges are about 50 mm content % to about 65 mm content %, about 50 mm content % to about 60 mm content %, about 50 mm content % to about 55 mm content %, about 55 mm content % to about 70 mm content %, about 55 mm content % to about 66 mm content %, about 55 mm content % to about 65 mm content %, about 55 mm content % to about 60 mm content %, about 60 mm content % to about 70 mm content %, or about 65 mm content % to about 70 mm content %.

[0095] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a 52 mm content % to 78 mm content %, a 52 mm content % to 77 mm content %, a 52 mm content % to 76 mm content %, a 52 mm content % to 75 mm content %, a 52 mm content % to 74 mm content %, a 52 mm content % to 70 mm content %, a 52 mm content % to 65 mm content %, a 52 mm content % to 60 mm content %, a 53 mm content % to 78 mm content %, a 53 mm content % to 77 mm content %, a 53 mm content % to 76 mm content %, a 53 mm content % to 75 mm content %, a 53 mm content % to 5 Content% to 74mm content%, 53mm content% to 70mm content%, 53mm content% to 65mm content%, 53mm content% to 60mm content%, 54mm content% to 78mm content%, 54mm content% to 77mm content%, 54mm content% to 76mm content%, 54mm content% to 75mm content%, 54mm content% to 74mm content%, 54mm content% to 70mm content%, 54mm content% to 67mm content%, 54mm content% to 66mm content%, 54mm content% to 65mm content%, 54mm content% to 60mm content%, 55mm content% to 78mm Content%, 55mm content% to 77mm content%, 55mm content% to 76mm content%, 55mm content% to 75mm content%, 55mm content% to 74mm content%, 55mm content% to 70mm content%, 55mm content% to 65mm content%, 55mm content% to 60mm content%, 58mm content% to 78mm content%, 58mm content% to 77mm content%, 58mm content% to 76mm content%, 58mm content% to 75mm content%, 58mm content% to 74mm content%, 58mm content% to 70mm content%, 58mm content% to 68mm content%, 60mm The triad tacticity of the present invention is within the range of 60mm content % to 78mm content %, 60mm content % to 77mm content %, 60mm content % to 76mm content %, 60mm content % to 75mm content %, 60mm content % to 74mm content %, 60mm content % to 70mm content %, or 60mm content % to 68mm content %, 61mm content % to 78mm content %, 61mm content % to 77mm content %, 61mm content % to 76mm content %, 61mm content % to 75mm content %, 61mm content % to 74mm content %, 61mm content % to 70mm content %, or 61mm content % to 68mm content %.

[0096] The triad tacticity of a polymer is the relative tacticity of a sequence of three adjacent propylene units (a chain consisting of head-to-tail bonds), expressed as a binary combination of meso (m) and racemic (r) sequences. The method for measuring triad tacticity is described in the Examples section below.

[0097] Typically, the crystallinity of the propylene-ethylene copolymer can be determined by the heat of crystallization. In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a crystallinity of about 20 J / g to about 30 J / g, about 20 J / g to about 35 J / g, about 20 J / g to about 40 J / g, about 20 J / g to about 45 J / g, about 20 J / g to about 50 J / g, about 20 J / g to about 55 J / g, about 25 J / g to about 30 J / g, about 25 J / g to about 50 J / g, about 25 J / g to about 55 J / g, about 27 J / g to about 40 J / g, about 28 J / g to about 60 J / g. or about 40 J / g to about 55 J / g, about 35 J / g to about 40 J / g, about 35 J / g to about 45 J / g, about 35 J / g to about 50 J / g, about 40 J / g to about 45 J / g, about 40 J / g to about 50 J / g, or about 40 J / g to about 55 J / g.

[0098] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a heat of crystallization (Hc, 20°C / min cooling rate, DSC) of at least 20 J / g, 21 J / g, 22 J / g, 23 J / g, 24 J / g, 25 J / g, 26 J / g, 27 J / g, 28 J / g, 29 J / g, 30 J / g, 31 J / g, 32 J / g, 33 J / g, 34 J / g, 35 J / g, 36 J / g, 37 J / g, 38 J / g, 39 J / g, or 40 J / g. Additionally or in the alternative, the propylene-ethylene copolymer may have a heat of crystallization (Hc, 20°C / min cooling rate, DSC) of less than 65, 64, 63, 62, 61, 60, 59, 58, 57, 56, 55, 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, or 40 J / g.

[0099] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a kinetic energy of about 1,000 cP to about 120,000 cP, about 1,000 cP to about 100,000 cP, about 1,000 cP to about 75,000 cP, about 1,000 cP to about 50,000 cP, about 1,000 cP to about 45,000 cP, about 1,000 cP to about 4 ... 0,000 cP, about 1,000 cP to about 35,000 cP, about 1,000 cP to about 30,000 cP, about 1,000 cP to about 25,000 cP, about 1,000 cP to about 20,000 cP, about 1,000 cP to about 15,000 cP, about 1,000 cP to about 10,000 cP, about 1,000 cP to about 5,000 cP, about 1,000 cP to about about 3,000 cP, 2,000 cP to about 120,000 cP, about 2,000 cP to about 100,000 cP, about 2,000 cP to about 75,000 cP, about 2,000 cP to about 50,000 cP, about 2,000 cP to about 45,000 cP, about 2,000 cP to about 40,000 cP, about 2,000 cP to about 35,000 cP, about 2,000 cP to about cP to about 30,000 cP, about 2,000 cP to about 25,000 cP, about 2,000 cP to about 20,000 cP, about 2,000 cP to about 15,000 cP, about 2,000 cP to about 10,000 cP, about 2,000 cP to about 5,000 cP, about 2,000 cP to about 7,000 cP, or about 2,000 cP to about 3,000 cP.

[0100] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a low viscosity (ASTM D-3236) ranging from about 1,000 cP to about 7,000 cP at 190° C. Other low viscosity ranges at 190° C. are from about 1,000 cP to about 5,000 cP, from about 1,000 cP to about 3,000 cP, or from about 2,000 cP to about 3,000 cP.

[0101] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a medium viscosity in the range of about 7,000 cP to about 15,000 cP at 190° C. Other medium viscosity ranges at 190° C. are about 7,000 cP to about 12,000 cP, about 7,000 cP to about 10,000 cP, or about 7,000 cP to about 9,000 cP.

[0102] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a high viscosity ranging from about 15,000 cP to about 27,000 cP at 190° C. Other high viscosity ranges at 190° C. are from about 15,000 cP to about 25,000 cP, from about 15,000 cP to about 20,000 cP, or from about 15,000 cP to about 18,000 cP.

[0103] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have an ultra high viscosity at 190°C greater than 27,000 cP, greater than 30,000 cP, greater than 35,000 cP, greater than 40,000 cP, greater than 45,000 cP, or greater than 50,000 cP. Other ultra high viscosity ranges at 190°C are about 27,000 cP to 150,000 cP, about 27,000 cP to about 125,000 cP, about 27,000 cP to about 100,000 cP, about 27,000 cP to about 75,000 cP, about 27,000 cP to about 70,000 cP, about 27,000 cP to about 65,000 cP, about 27,000 cP to about 60,000 cP, about 27,000 cP to about 55,000 cP, about 27,000 cP to about 50,000 cP, about 27,000 cP to about 45,000 cP, about 27,000 cP to about 40,000 cP, or about 27,000 cP to about 35,000 cP.

[0104] Typically, the needle penetration force of propylene-ethylene copolymers can be changed and optimized by controlling the comonomer content, triad stereoregularity and crystallinity of propylene-ethylene copolymers. In one embodiment or in combination with any embodiment mentioned herein, propylene-ethylene copolymers can have a needle penetration force in the range of about 0.1 decimeter to about 21 decimeters ("dmm"), as measured according to ASTM D5. Other exemplary needle penetration ranges are 1dmm to 19dmm, 1dmm to 16dmm, 2dmm to 10dmm, 2dmm to 8dmm, 3dmm to 21dmm, 3dmm to 19dmm, 3dmm to 16dmm, 3dmm to 10dmm, 3dmm to 8dmm, 4dmm to 21dmm, 4dmm to 19dmm, 4dmm to 16dmm, 4dmm to 10dmm, 4dmm to 8dmm2dmm to about 21dmm. Other ranges are 2dmm to 19dmm, 2dmm to 16dmm, 2dmm to 10dmm, 2dmm to 8dmm, 3dmm to 21dmm, 3dmm to 19dmm, 3dmm to 16dmm, 3dmm to 10dmm, 3dmm to 8dmm, 4dmm to 21dmm, 4dmm to 19dmm, 4dmm to 16dmm, 4dmm to 10dmm or 4dmm to 8dmm.

[0105] In general, the tensile strength at break of the propylene-ethylene copolymer can be varied and optimized by controlling the comonomer content, triad tacticity, crystallinity, and viscosity of the propylene-ethylene copolymer. In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a tensile strength of about 1.5 MPa to about 25 MPa, about 1.5 MPa to about 18 MPa, about 1.5 MPa to about 17 MPa, about 3 MPa to about 17 MPa, about 1.5 MPa to about 14 MPa, about 3 MPa to about 18 MPa, about 3 MPa to about 15 MPa, about 3 MPa to about 14 MPa, about 3 MPa to about 12 MPa, about 3 MPa to about 10 MPa, about 3 MPa to about 8 MPa, about 3 MPa to about 6 MPa, about 4 MPa to about 14 MPa, about 4 MPa to about 12 MPa, about Tensile Strength at Break (MPa) in the range of from about 4 MPa to about 10 MPa, from about 4 MPa to about 8 MPa, from about 4 MPa to about 6 MPa, from about 5 MPa to about 14 MPa, from about 5 MPa to about 12 MPa, from about 5 MPa to about 10 MPa, 5 MPa to about 8 MPa, from about 6 MPa to about 14 MPa, from about 6 MPa to about 12 MPa, from about 6 MPa to about 10 MPa, from about 6 MPa to about 8 MPa, from about 7 MPa to about 14 MPa, from about 7 MPa to about 12 MPa, from about 7 MPa to about 10 MPa, from about 8 MPa to about 14 MPa, or from about 8 MPa to about 12 MPa, as measured according to ASTM D412.

[0106] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have an elongation at break (MPa) greater than 100%, greater than 200%, greater than 300%, greater than 350%, greater than 375%, greater than 400%, greater than 425%, greater than 450%, greater than 475%, and greater than 500%, as measured according to ASTM D 412. For example, the propylene-ethylene copolymer can have an elongation at break (MPa) in the range of 300% to 2,000%, 300% to 1,000%, 300% to about 800%.

[0107] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a molecular weight of about 18 J / g to about 45 J / g, about 10 J / g to about 36 J / g, about 10 J / g to about 30 J / g, about 10 J / g to about 25 J / g, about 10 J / g to about 20 J / g, about 10 J / g to about 15 J / g, about 10 J / g to about 36 J / g, about 10 J / g to about 30 J / g, about 10 J / g to about 25 J / g, about 10 J / g to about 20 J / g, about 10 J / g to about 15 J / g, 15 J / g to about 36 J / g, about 15 J / g to about 30 J / g, about 15 J / g to about 25 J / g, about 15 J / g to about 20 J / g, about 20 J / g to about 36 J / g, about 20 J / g to about 30 J / g, or about 20 J / g to about 25 J / g.

[0108] Table 1 shows various embodiments of propylene-ethylene copolymers. Generally, the ethylene copolymers of the present invention contain from about 89 wt% to about 98 wt% propylene, have a Ring and Ball softening point of from about 135°C to about 165°C, a triad tacticity of from about 50% to about 78%, and at least one other property selected from Table 1. For ease of reference and not to be considered limiting of the present invention, the polymers are designated in Tables 1A and 1B as four "categories": (1) high viscosity, high elongation, and high RBSP polymers; (2) medium viscosity, high elongation, and high RBSP polymers; (3) ultra-high viscosity and high RBSP polymers; and (4) low viscosity and high RBSP polymers.

[0109] Table 1A

[0110]

[0111] Table 1B

[0112]

[0113] In one embodiment or in combination with any embodiment mentioned herein, the copolymers described herein do not exhibit significant color changes when subjected to storage conditions at elevated temperatures for extended periods of time. Before any aging occurs due to storage, the copolymers of the present invention may have an initial Gardner color of less than 4, 3, 2, or 1, as measured according to ASTM D1544. After heat aging at 177° C. for at least 96 hours, the copolymers of the present invention may exhibit a final Gardner color of less than 7, 5, 3, or 2, as measured according to ASTM D1544. Thus, the copolymers of the present invention may retain the desired color even after long-term storage and exposure.

[0114] In addition, the copolymers described herein can be amorphous or semi-crystalline. As used herein, "amorphous" means that the copolymer has a crystallinity of less than 5%, as measured using differential scanning calorimetry ("DSC") according to ASTM E 794-85. As used herein, "semi-crystalline" means that the copolymer has a crystallinity in the range of 5% to 40%, as measured using DSC at a scanning rate of 20°C / min according to ASTM E 794-85. In various embodiments, the copolymer may have a crystallinity of not more than 60%, 40%, 30%, 20%, 10%, 5%, 4%, 3%, 2% or 1%, as measured using DSC at a scanning rate of 20°C / min according to ASTM E 794-85. Additionally or in the alternative, the copolymer may have a crystallinity of less than 60%, 50%, 45%, 40%, 35%, 30%, 25%, 24%, 23%, or 22%, as measured using DSC at 20°C / min according to ASTM E 794-85. For example, the copolymer may have a crystallinity in the range of 2% to 50%, 3% to 46%, 4% to 40%, 4% to 30%, 4% to 20%, 16% to 25%, 16% to 23%, 17% to 25%, 17% to 23%, 20% to 35%, or 20% to 30%, as measured using DSC at 20°C / min according to ASTM E 794-85.

[0115] Process for producing propylene-ethylene copolymers

[0116] An object of the present invention is to provide a group of propylene-ethylene copolymers that can be used in high heat resistance applications and exhibit improved mechanical strength. Without wishing to be bound by theory, it is believed that the unique heat resistance and ability to support loads at high temperatures can be achieved due to a combination of several different copolymer characteristics such as the propylene / ethylene content of the copolymer, the triad stereoregularity content (mm%) of the copolymer, the ring and ball softening point of the copolymer, and the heat of crystallization of the copolymer. The objects of the present invention are achieved by specific ranges of polymer compositions, more specifically, propylene / ethylene comonomer ratios, and preferred ranges of propylene triad stereoregularity content (mm%). These polymer compositions are achieved by improved process conditions.

[0117] In one embodiment or in combination with any of the embodiments mentioned herein, the copolymer may be produced by reacting propylene monomer and ethylene monomer in the presence of a catalyst system comprising at least one electron donor.

[0118] In one embodiment or in combination with any embodiment mentioned herein, the catalyst system may comprise a Ziegler-Natta catalyst. According to one or more embodiments, the Ziegler-Natta catalyst may contain a titanium-containing component, an aluminum component, and an electron donor. In certain embodiments, the catalyst comprises titanium chloride on a magnesium chloride support.

[0119] In certain embodiments, the catalyst system may include a heterogeneously supported catalyst system formed by combining a titanium compound with an organoaluminum cocatalyst. In various embodiments, the cocatalyst may include an alkylaluminum cocatalyst such as triethylaluminum ("TEAL").

[0120] In one or more embodiments, the catalyst system can have an aluminum to titanium molar ratio of at least 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or 15:1 and / or no greater than 100:1, 50:1, 35:1, or 25:1. Further, the catalyst system can have an aluminum to titanium molar ratio in the range of 1:1 to 100:1, 5:1 to 50:1, 10:1 to 35:1, or 15:1 to 25:1. Additionally or alternatively, in various embodiments, the catalyst system can have an aluminum to silicon molar ratio of at least 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, or 6:1 and / or no greater than 100:1, 50:1, 35:1, 20:1, 15:1, 10:1, or 8:1. Additionally, the catalyst system can have a molar ratio of aluminum to silicon in the range of 0.5:1 to 100:1, 1:1 to 50:1, 2:1 to 35:1, 2:1 to 20:1, 2:1 to 15:1, 2:1 to 10:1, or 2:1 to 8:1.

[0121] Electron donors can increase the stereospecificity of the copolymer. However, it may be important to strictly regulate the content of electron donors because they can inhibit catalyst activity to unacceptable levels in some cases. Electron donors used in the polymerization process may include, for example, organic esters, ethers, alcohols, amines, ketones, phenols, phosphines and / or organosilanes. In addition, the catalyst system may contain internal donors and / or external donors.

[0122] For Ziegler-Natta catalyst systems, many generations of internal donors have been developed, as defined in J. Severn and RL Jones Jr, "Stereospecific α-Olefin Polymerization with Heterogeneous Catalysts", Handbook of Transition Metal Polymerization Catalysts (2018), Chapter 9, pp. 229-312, the entire contents of which are incorporated herein by reference. The Ziegler-Natta catalyst generations described by Severn and Jones are as follows:

[0123] 3rd Generation Ziegler-Natta Catalysts (Benzoates): The third generation catalysts typically comprise MgCl2, TiCl4 and an internal electron donor in combination with an alkyl aluminum co-catalyst such as Al(CH2CH3)3. An "external" electron donor may be added to the catalyst system. The internal donor in the third generation catalysts is typically ethyl benzoate, which is used in combination with a second aromatic ester such as methyl p-toluate or ethyl p-ethoxybenzoate (PEEB) as an external donor. An external donor is required because most of the internal donor is lost in reactions involving co-catalysts such as alkylation and / or complexation reactions. The external donor largely replaces the internal donor in the solid catalyst, thereby maintaining high catalyst stereospecificity.

[0124] 4th Generation Ziegler-Natta Catalysts (Phthalates): The 4th generation catalysts contain MgCl2, TiCl4 and an internal electron donor, which are combined with an alkyl aluminum cocatalyst such as Al(CH2CH3)3. And an "external" electron donor can be added to the catalyst system. The internal donor in the 4th generation catalyst is based on phthalate / alkoxysilane. It has been found that bidentate phthalate donors can form strong chelate complexes with the tetracoordinated Mg atom on the (110) face of MgCl2 or binuclear complexes with two pentacoordinated Mg atoms on the (100) face.

[0125] 5th Generation Ziegler-Natta Catalysts (Diethers and Succinates): It has been found that when the catalyst is contacted with an Al(CH2CH3)3 cocatalyst, certain diether compounds, particularly those in which the oxygen-oxygen distance is between 2,2-disubstituted-1,3-dimethoxypropanes in the range (similar to those of alkoxysilane external donors) are not extracted. Therefore, high stereospecificity can be obtained even in the absence of external donors for fifth-generation diether catalyst systems. Fifth-generation diether catalyst systems can show particularly high polymerization activity and good stability. They also have a relatively narrow molecular weight distribution (MWD) and show high sensitivity to hydrogen. Recently, new internal donor compounds based on aliphatic dicarboxylates have been used, such as malonates and glutarates, especially succinates and polyol esters. Alkoxysilanes are generally used as external donors.

[0126] 6th Generation Ziegler-Natta Catalysts (Phthalates Replacement): The new 1,2-phenylene dibenzoate internal donors used in 6th Generation Ziegler-Natta catalysts are important phthalates replacements. In addition, there is an increasing number of disclosures about mixed internal donors, for example, blending succinates and diethers, or blending succinates and dimethoxytoluene. 6th Generation catalysts can also produce high stereospecificity in the absence of external donors. Therefore, depending on the crystallinity target, an external donor may or may not be used to achieve the desired crystallinity target.

[0127] In one embodiment or in combination with any of the embodiments mentioned herein, Ziegler-Natta catalyst systems of higher generations than the third and fourth generations can be operated in the absence of an external electron donor. Depending on the crystallinity target, when using the fifth and sixth generation catalyst systems, an external electron donor may or may not be used to achieve the desired crystallinity target.

[0128] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system may comprise a third generation Ziegler-Natta catalyst, a fourth generation Ziegler-Natta catalyst, a fifth generation Ziegler-Natta catalyst, or a sixth generation Ziegler-Natta catalyst.

[0129] Typically, the catalyst system comprises at least one external electron donor. In one embodiment or in combination with any of the embodiments mentioned herein, the external electron donor comprises at least one alkoxysilane, such as a "D" donor (e.g., dicyclopentyldimethoxysilane), a "C" donor (e.g., cyclohexylmethyldimethoxysilane), or a combination thereof. Furthermore, in some embodiments, the alkoxysilane may comprise, consist essentially of, or consist entirely of a "D" donor or a "C" donor.

[0130] In one embodiment of the invention, no electron donor is used in the process.

[0131] It has been observed that the addition of the above-mentioned external donors to the catalyst system can increase the hardness (i.e., reduce needle penetration) and viscosity of the copolymer. However, contrary to what has been previously observed in the art, the above-mentioned electron donors can reduce rather than increase the softening point of the copolymer produced. In addition, it has been observed that when the above-mentioned electron donors are used, substantially all (i.e., greater than 95%) of the ethylene added to the reactor during the polymerization process can react. Therefore, this can produce copolymers with higher ethylene content and lower propylene content. Therefore, when the above-mentioned electron donors are used, propylene-ethylene copolymers with higher ethylene content but still exhibiting a desired balance between softening point and hardness can be produced.

[0132] Moreover, according to various embodiments, the catalyst system can have an external electron donor to titanium molar ratio of at least 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, or 4:1 and / or less than 10:1, 9:1, or 8: 1. Additionally or alternatively, the catalyst system can have a molar ratio of 0.1:1 to 10:1, 0.5:1 to 10:1, 1:1 to 10:1, 1.5:1 to 10:1, 2:1 to 10:1, 2.5:1 to 10:1, 3:1 to 10:1, 3.5:1 to 10:1, 4:1 to 10:1, 0.5:1 to 9:1, 1:1 to 9:1, 1.5:1 to 9:1. 1 to 8:1, 2:1 to 9:1, 2.5:1 to 9:1, 3:1 to 9:1, 3.5:1 to 9:1, 4:1 to 9:1, 0.5:1 to 8:1, 1:1 to 8:1, 1.5:1 to 8:1, 2:1 to 8:1, 2.5:1 to 8:1, 3:1 to 8:1, 3.5:1 to 8:1, or 4:1 to 8:1.

[0133] Additionally or alternatively, in various embodiments, the catalyst system may comprise a TEAL co-catalyst to electron donor molar ratio of at least 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, or 6: 1 and / or no greater than 100: 1, 50: 1, 35: 1, 20: 1, 15: 1, 10: 1, or 8: 1. Further, the catalyst system may comprise a TEAL co-catalyst to electron donor molar ratio in a range of 0.5: 1 to 100: 1, 1: 1 to 50: 1, 2: 1 to 35: 1, 2: 1 to 20: 1, 2: 1 to 15: 1, 2: 1 to 10: 1, or 2: 1 to 8: 1.

[0134] In certain embodiments, the type of electron donor can affect the necessary TEAL / electron donor ratio. For example, in embodiments where the electron donor is a "D" donor or a "C" donor, the TEAL / electron donor ratio can be less than 20:1.

[0135] The catalyst system can exhibit a catalyst activity in the range of 200 g / g to 2,000 g / g, 400 g / g to 1,200 g / g, 500 g / g to 1,000 g / g, 1,000 g / g to 6,000 g / g, or 6,000 g / g to 18,000 g / g. The catalyst activity is calculated by measuring the ratio of the weight of polymer produced in the reactor to the weight of catalyst charged to the reactor. These measurements are based on a one hour reaction time.

[0136] Since the addition of external donors can increase viscosity and molecular weight, it may be desirable to add hydrogen to act as a chain terminator during polymerization. For example, the process can be conducted at a hydrogen pressure ranging from 5 psig to 100 psig, from 10 psig to 80 psig, or from 15 psig to 50 psig.

[0137] In one embodiment or in combination with any of the embodiments mentioned herein, the polymerization reaction can occur at a temperature of 160° C. or less, 155° C. or less, 150° C. or less, or 145° C. or less, 140° C. or less, in the range of 100° C. to 200° C., 110° C. to 180° C., 110° C. to 155° C., 120° C. to 160° C., 140° C. to 155° C., or 120° C. to 150° C. In addition, the polymerization reaction can be carried out at a pressure in the range of 500 psig to 2,000 psig, 600 psig to 1,500 psig, 700 psig to 1,250 psig, or 800 psig to 1,100 psig.

[0138] In embodiments of the present invention, the ratio of the ethylene stream to the propylene stream entering the polymerization reaction may be in the range of 0.1:100 to 18:100, 0.1:100 to 10:100, 0.1:100 to 5:100, 0.1:100 to 4:100, 0.5:100 to 3:100, 0.5:100 to 2:100, 0.5:100 to 1.5:100, 0.5:100 to 1:100, 1:100 to 4:100, 1:100 to 3:100, 1:100 to 2:100, 1.5:100 to 4:100, 1.5:100 to 3:100, 1.5:100 to 2:100, 2:100 to 3 ... 00, 7:100 to 18:100, 7:100 to 14:100, 7:100 to 12:100, 7:100 to 10:100, 8:100 to 18:100, 8:100 to 14:100, 8:100 to 12:100, or 8:100 to 10:100.

[0139] In embodiments of the invention, the ratio of the hydrogen flow to the propylene flow entering the polymerization reaction may be in the range of 0.03:100 to 0.5:100, 0.04:100 to 0.4:100, 0.15:100 to 0.4:100, 0:100 to 0.3:100, 0:100 to 0.2:100, 0.100:100 to 0.02:100, 0:100 to 0.01:100, 0.01:100 to 0.02:100, 0.04:100 to 0.2:100, 0.05:100 to 0.1:100, 0.07:100 to 0.3:100, or 0.08:100 to 0.4:100.

[0140] In certain embodiments, the reactor may include a stirred reactor, and the residence time of the polymerization reaction in the reactor may be in the range of 0.1 hour to 6 hours, 0.5 hour to 4 hours, or 1 hour to 2 hours. In some embodiments, the residence time of the polymerization reaction in the reactor may be in the range of 6 hours to 72 hours, 16 hours to 36 hours, 16 hours to 24 hours, 12 hours to 48 hours, or 12 hours to 24 hours. In other embodiments, the reactor may include a loop reactor, and the residence time of the polymerization reaction in the reactor may be in the range of 8 hours to 72 hours, 12 hours to 48 hours, 12 hours to 24 hours, or 16 hours to 36 hours. In one embodiment or in combination with any embodiment mentioned herein, ethylene may be added to the reactor as a gas and propylene may be added as a liquid.

[0141] End uses containing heat-resistant propylene-ethylene copolymers

[0142] The inventive propylene-ethylene copolymers described herein and compositions comprising these copolymers are useful in a wide variety of applications including, for example, adhesives (e.g., automotive adhesives, woodworking adhesives, packaging adhesives), sealants, caulks, roofing membranes, waterproofing membranes, compounds and underlayments, carpets, laminates, laminated products, tapes (e.g., security tapes, water-foamed tapes, adhesive tapes, sealing tapes, cloth-based reinforcement tapes, plywood tapes, reinforced and non-reinforced paper tapes, boxing tapes, paper tapes, packaging tapes), labels, adhesives, polymer blends, wire coatings, molding products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, asphalt modification, asphalt modification, cable impregnation / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, glass fiber reinforced plastics, plastic fiber reinforced compounds, wood plastic composites, lost wax precision castings, investment casting wax components, candles, windows, films, gaskets, seals, O-rings, automotive molded parts, automotive extruded parts, apparel products, rubber additives / processing aids and fibers.

[0143] Films comprising the propylene-ethylene copolymers of the present invention described herein and compositions comprising these copolymers include, but are not limited to, multilayer films, coextruded films, calendered films, and cast films. Laminates comprising the propylene-ethylene polymers of the present invention or compositions comprising the propylene-ethylene polymers of the present invention include, but are not limited to, paper-foil laminates, paper-film laminates, and nonwoven-film laminates.

[0144] Adhesive compositions comprising the inventive propylene-ethylene copolymers described herein and compositions comprising these copolymers include packaging adhesives, food contact grade adhesives, indirect food contact packaging adhesives, product assembly adhesives, woodworking adhesives, edge banding adhesives, profile packaging adhesives, flooring adhesives, automotive assembly adhesives, structural adhesives, mattress adhesives, pressure sensitive adhesives (PSA), PSA tapes, PSA labels, PSA protective films, self-adhesive films, laminating adhesives, flexible packaging adhesives, heat seal adhesives, industrial adhesives, sanitary nonwoven construction adhesives, sanitary core integrity adhesives, or sanitary elastic attachment adhesives.

[0145] In certain embodiments, copolymers as described herein can be used for adhesives, such as, for example, hot melt adhesives, water-based adhesives, solvent-based adhesives, hot melt pressure-sensitive adhesives, solvent-based pressure-sensitive adhesives, hot melt nonwoven / hygienic adhesives, hot melt product assembly adhesives, hot melt woodworking adhesives, hot melt automotive parts assembly adhesives, hot melt laminating adhesives, and hot melt packaging adhesives. In particular, due to the unique combination of softening point, heat resistance, and needle penetration as described above, the adhesive produced by the copolymers of the present invention can be used in a large number of end products, including hygienic packaging materials, household appliances, automotive parts, woodworking and packaging applications requiring heat resistance. In many embodiments, various properties of the copolymers of the present invention can be selected, such as softening point and needle penetration, to be suitable for the expected end use of the composition incorporating the heat-resistant copolymers of the present invention.

[0146] In certain embodiments, the copolymers of the present invention can be used to produce adhesive compositions that can be used for automotive interior components, packaging, product assembly, heat sealing, lamination, gap sealing (e.g., cable filling, caulking, and window sealants), woodworking, edge banding, and / or profile packaging. The terms "adhesive," "adhesive composition," and "composition" are used interchangeably.

[0147] In one embodiment or with any embodiment combination mentioned herein, adhesive composition of the present invention comprises hot melt adhesive.Hot melt adhesive can be applied to substrate and cools down to harden the adhesive layer in its molten state.This type of adhesive is widely used in various commercial and industrial applications, such as product assembly, lamination and packaging.In these applications, adhesive is applied to at least one substrate to bond this substrate to second similar or different substrate.

[0148] Adhesive, sealant and other product formulators and users generally desire thermally stable, low color hot melt adhesives having a favorable balance of physical properties, including temperature resistance, chemical resistance, cohesive strength, viscosity, adhesion to various substrates, and open and set times that can be tailored for specific uses and application conditions. The balance of desired properties varies with the application, and the inventive hot melt compositions described herein provide an improved balance of properties for a variety of end uses.

[0149] The hot melt adhesive composition can have a melt rheology and thermal stability suitable for conventional hot melt adhesive application equipment. In one embodiment or in combination with any embodiment mentioned herein, the blended components of the hot melt adhesive composition have a low melt viscosity at the application temperature, thereby facilitating the composition to flow through a coating device (e.g., a coating die or nozzle).

[0150] The hot melt adhesive composition can be used to bond a variety of substrates including, for example, cardboard, coated cardboard, paperboard, fiberboard, virgin and recycled kraft paper, high density and low density kraft paper, wood chip plywood, treated and coated kraft and wood chip plywood and their corrugated forms, clay-coated wood chip plywood cartons, composites, leather, polymeric films (e.g., polyolefin films (e.g., polyethylene and polypropylene), polyvinylidene chloride films, ethylene vinyl acetate films, polyester films, metallized polymeric films, multilayer films, and combinations thereof), fibers and substrates made from fibers (e.g., virgin fibers, recycled fibers, synthetic polymer fibers, cellulosic fibers, and combinations thereof), release liners, porous substrates (e.g., woven webs, nonwoven webs, nonwoven scrims, and perforated films), cellulosic substrates, sheets (e.g., paper and fiber sheets), paper products, tape backings, and combinations thereof. Useful composite materials include, for example, wood chip plywood laminated to metal foil (e.g., aluminum foil) (which may optionally be laminated to at least one layer of a polymeric film), wood chip plywood bonded to a film, kraft paper bonded to a film (e.g., polyethylene film), and combinations thereof.

[0151] The hot melt adhesive composition can be used to bond a first substrate to a second substrate in a variety of applications and constructions, including, for example, packages, bags, boxes, cartons, cases, trays, multi-wall bags, articles comprising accessories (e.g., straws attached to beverage cartons), ream wrappers, cigarettes (e.g., plug wrap), filters (e.g., pleated filters and filter frames), bindings, footwear, disposable absorbent articles (e.g., disposable diapers, sanitary napkins, medical dressings (e.g., wound care products), bandages, surgical pads, drapes, surgical gowns, and meat packaging products), paper products (including, for example, paper towels (e.g., multi-purpose towels), toilet paper, facial tissue, wipes, tissues, towels (e.g., paper towels)), sheets, plywood, mattress covers, automotive foils, TPO compounds, and components of absorbent articles (including, for example, absorbent elements, absorbent cores, impermeable layers (e.g., backsheets), tissues (e.g., wrapping tissues), acquisition layers, and woven and nonwoven web layers (e.g., topsheets, absorbent tissues), and combinations thereof.

[0152] The hot melt adhesive composition can also be used to form laminates of porous substrates and polymeric films, such as those used to make disposable articles, including, for example, medical drapes, medical gowns, sheets, feminine hygiene products, diapers, adult incontinence products, absorbent pads for animals (e.g., pet pads) and absorbent pads for humans (e.g., body and corpses), and combinations thereof.

[0153] The hot melt adhesive composition can be applied to the substrate in any useful form using any suitable application method, which includes, for example, as fibers, as coatings (e.g., continuous coatings and discontinuous coatings (e.g., random, patterns, and arrays)), as beads, as films (e.g., continuous films and discontinuous films), and combinations thereof, including, for example, slot coating, curtain coating, spraying (e.g., spiral spraying, random spraying, and random fiberization (e.g., melt blowing)), foaming, extrusion (e.g., application of beads, fine wire extrusion, single screw extrusion, and twin screw extrusion), wheel application, non-contact coating, contact coating, gravure printing, gravure printing rollers, roller coating, transfer coating, screen printing, flexographic printing, and combinations thereof.

[0154] One embodiment of the present invention relates to a vehicle having a vehicle interior material (preferably an automobile interior material) comprising a skin material (preferably a polyolefin-based substrate) to which a hot-melt composition is applied. Examples of vehicles according to the present invention include, but are not particularly limited to, vehicles such as motor vehicles (cars), motor bicycles (motorcycles), buses, trucks, and trams. In this specification, although the term "automobile interior material" is used in some sentences, the term can also be understood to mean an interior material for vehicles other than automobiles, as long as the hot-melt composition of the present invention can be applied.

[0155] The compositions of the present invention can be used to form bonds to produce laminates and multilayer laminates.The terms "laminate" and "multilayer laminate" are used interchangeably.

[0156] The compositions of the present invention according to one or more embodiments of the present invention can be bonded to various adherends, including but not limited to: cellulosic polymer materials such as paper, cotton, linen, cloth and wood; synthetic polymer materials, including polyolefin resins such as polypropylene (PP) and polyethylene (PE), styrene resins such as polystyrene, styrene-butadiene block copolymers (SBS resins), styrene-acrylonitrile copolymers (AS resins), acrylonitrile-ethylene / propylene styrene copolymers (AES resins) and acrylonitrile-butadiene-styrene copolymers (ABS resins), polycarbonate resins (PC resins), PC-ABS resins, ( The invention relates to the invention to a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention. The adhesive layer of the present invention can be a kind of adhesive layer of the present invention.

[0157] Laminates comprising the polymer or composition of the present invention can be suitably used in applications where covering materials and shaped articles are used as adherends, such as automotive interior materials (e.g., ceiling materials for automotive interior parts, door components for automotive interior parts, instrument panel components for automotive interior parts, instrument panels), components for home appliances (e.g., housings of personal computers, frames of flat-panel televisions), and housing materials (e.g., interior wall panels, decorative films, etc.).

[0158] Covering material refers to a material that has been formed into a film, sheet, foam, or any type of nonwoven or woven material. Examples include decorative polymer sheets made from polyvinyl chloride, various polyolefins, ABS, thermoplastic polyolefin compounds (TPO) such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, polyester nonwoven fabrics, fleece knits, fabrics, polyurethane artificial leather, and polyolefin foams formed primarily of polypropylene, polyethylene, polybutylene, or copolymers of these olefins. Examples of shaped articles include injection molded articles of various polymer materials such as ABS, PC / ABS, polyolefins, glass fiber reinforced polyolefins, and glass fiber reinforced nylons; and wooden shaped articles and wooden boards prepared by encapsulating materials such as wood chips or wood powder in thermosetting resins or polyolefin resins by hot compression molding.

[0159] When preparing a multilayer laminate by bonding a covering material such as a decorative sheet to a shaped article used as a base material via an adhesive layer comprising the propylene-ethylene polymer or hot melt adhesive composition of the present invention, various forming methods such as thermal lamination, vacuum forming, vacuum pressure forming, hot pressing, hot rolling and hot stamping can be used. Among the shaped articles made of the above materials, the curved shaped article means a shaped article having a planar arc surface as a surface to be bonded to the covering material. Such shaped articles are used to form a shape skeleton in the housing of an automotive interior or a household appliance.

[0160] In one embodiment or in combination with any embodiment mentioned herein, a method is provided wherein at least one composition useful in the present invention may be applied to a first substrate, or optionally, to two or more substrates, wherein each substrate may be independently selected, wherein the first substrate and the second substrate may each be independently selected from the group consisting of: poly(acrylonitrile butadiene styrene) (ABS); polycarbonate (PC); PC-ABS blends; thermoplastic polyolefins such as polypropylene (PP); TPO compounds; textiles, such as fabric materials, meshes, plywood, birch wood, plywood, MDF boards, wovens and / or nonwovens; foam materials; leather materials; vinyl materials; and / or other materials that will be apparent to those of ordinary skill in the art. These materials may or may not be used with fillers.

[0161] Typical but non-limiting industrial applications of hot melt adhesive compositions include packaging, particularly packaging for high temperature applications, such as boxes and cartons in warehouses, woodworking, and vehicle (e.g., automotive) interior trim assembly. Traditional end-use applications such as bookbinding, disposable hygiene consumer products, and labels will also benefit from heat resistance and end-use efficiency in an automated manner for applying hot melt adhesive compositions to various substrates.

[0162] In addition, in various embodiments, the inventive copolymers described herein can also be used to modify existing polymer blends typically used for plastics, elastomer applications, roofing applications, asphalt modification, cable filling, and tire modification. The inventive copolymers can improve the adhesion, processability, stability, viscoelasticity, thermal properties, and mechanical properties of these polymer blends.

[0163] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymers of the present invention may be modified to produce graft copolymers. In such embodiments, the copolymers of the present invention may be grafted with maleic anhydride, fumarate and maleate esters, methacrylates (e.g., glycidyl methacrylate and hydroxyethyl methacrylate), methacrylic acid, vinyl derivatives, silane derivatives, or combinations thereof. These graft copolymers may be produced using any conventional method known in the art, including, for example, transesterification and free radical-induced coupling.

[0164] The above-mentioned various end uses and end products can use the copolymer of the present invention alone or in combination with other additives and polymers. Suitable polymers that can be combined with the copolymer of the present invention to form a polymer blend can include, for example, isoprene-based block copolymers; butadiene-based block copolymers; hydrogenated block copolymers; styrene-ethylene / butylene-styrene block copolymers (SEBS); styrene-isoprene-styrene block copolymers (SIS); styrene-ethylene / propylene-styrene (SEPS); ethylene vinyl acetate copolymers; polyesters; polyester-based copolymers; chloroprene rubber; urethanes; acrylic acid; polyacrylates; acrylate copolymers, such as but not limited to ethylene acrylic acid copolymers, ethylene n-butyl acrylate copolymers, and ethylene methyl acrylate copolymers; polyetheretherketones; polyamides; styrene block copolymers; hydrogenated styrene block copolymers; random styrene copolymers; ethylene-propylene rubber; ethylene vinyl acetate copolymers; butyl rubber; styrene-butadiene rubber; nitrile rubber; natural rubber; polyisoprene; polyisobutylene; polyvinyl acetate; and polyolefins.

[0165] The polyolefin used in the present invention with the inventive propylene-ethylene copolymer can be any polyolefin known in the art. In one embodiment or in combination with any embodiment mentioned herein, the polyolefin can be at least one polyolefin selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, α-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-prepared thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers (including ethylene-propylene-butene terpolymers), propylene and linear or branched C4-C4 copolymers. 10 Copolymers produced from α-olefin monomers, consisting of ethylene and linear or branched C4-C 10 Copolymers and functionalized polyolefins produced from α-olefin monomers.

[0166] There are a variety of methods for functionalizing polymers in the art that can be used with the polymers described herein. These methods include selective oxidation, free radical grafting, ozonolysis, epoxidation, etc. Functionalized components include, but are not limited to, functionalized olefin polymers (such as functionalized C2 to C 40 Homopolymer, functionalized C2 to C 40 Functionalized olefin polymers and copolymers useful in the present invention include maleated polyethylene, maleated metallocene polyethylene, maleated metallocene polypropylene, maleated ethylene propylene rubber, maleated polypropylene, maleated ethylene copolymers, functionalized polyisobutylene (typically functionalized with maleic anhydride, typically to form succinic anhydride), and the like.

[0167] In one embodiment or with any embodiment combination mentioned herein, propylene-ethylene copolymer of the present invention as herein described can be used for producing hot-melt adhesive.According to one or more embodiments, adhesive composition can comprise at least 1 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight, 15 % by weight, 20 % by weight, 23 % by weight, 25 % by weight, 30 % by weight, 35 % by weight, 37 % by weight, 40 % by weight, 45 % by weight, 47 % by weight or 50 % by weight and / or be not more than 95 % by weight, 90 % by weight, 85 % by weight, 80 % by weight, 76 % by weight, 75 % by weight, 70 % by weight, 66 % by weight, 63 % by weight, 60 % by weight, 59 % by weight, 56 % by weight, 55 % by weight, 52 % by weight, 50 % by weight, 45 % by weight, 40 % by weight, 35 % by weight, 30 % by weight, 25 % by weight, 20 % by weight, 15 % by weight or 10 % by weight of copolymer of the present invention. In addition, the adhesive composition can include 1% to 95% by weight, 5% to 90% by weight, 10% to 80% by weight, 20% to 70% by weight, 30% to 60% by weight, 40% to 55% by weight, 50% to 80% by weight, 50% to 70% by weight, 30% to 90% by weight, 30% to 80% by weight, 30% to 70% by weight, 30% to 60% by weight, 30% to 50% by weight or 30% to 40% by weight of the copolymer of the present invention. In certain embodiments, the adhesive composition can be composed entirely of the copolymer of the present invention.

[0168] Additionally, depending on the intended end use, these hot melt adhesive compositions may also contain various additives including, for example, polymers, tackifiers, processing oils, waxes, antioxidants, plasticizers, pigments, and fillers.

[0169] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition can include at least 1 wt %, 5 wt %, 6 wt %, 7 wt %, 10 wt %, 12 wt %, 20 wt %, 23 wt %, 30 wt %, 35 wt %, 40 wt % or 47 wt % and / or be no more than 90 wt %, 80 wt %, 70 wt %, 56 wt % or 55 wt % of at least one polymer different from copolymer of the present invention. In addition, the adhesive can include at least one polymer different from copolymer of the present invention in the range of 10 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 55 wt %. In other embodiments, adhesive can comprise at least 1 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 15 wt %, 20 wt %, 23 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 47 wt % or 50 wt % of at least one polymer that is different from copolymer of the present invention. These polymers can include but are not limited to any polymer in the polymer listed above.

[0170] In addition, it has been found that the blend of copolymer of the present invention and various types of polyolefin can provide the tackiness agent with improved adhesion, cohesive strength, temperature resistance, viscosity and open time and setting time.Therefore, in various embodiments, the above-mentioned polymer that can be combined with propylene-ethylene copolymer of the present invention can comprise at least one polyolefin.In certain embodiments, except comprising propylene-ethylene copolymer of the present invention, tackiness agent also can comprise at least 1 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 10 % by weight, 12 % by weight, 15 % by weight, 20 % by weight, 23 % by weight, 25 % by weight, 30 % by weight, 35 % by weight, 40 % by weight, 45 % by weight, 47 % by weight or 50 % by weight of at least one polyolefin. Additionally or in the alternative, in addition to comprising the propylene-ethylene copolymer of the present invention, the adhesive composition may also comprise no more than 99 wt %, 95 wt %, 90 wt %, 85 wt %, 80 wt %, 75 wt %, 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %, 15 wt %, 10 wt %, 7 wt % or 5 wt % of at least one polyolefin. For example, based on the gross weight, the adhesive composition may comprise at least one polyolefin in the range of 1 wt % to 90 wt %, 1 wt % to 60 wt %, 1 wt % to 40 wt %, 1 wt % to 20 wt %, 10 wt % to 90 wt %, 20 wt % to 80 wt %, 20 wt % to 40 wt %, 30 wt % to 70 wt %, 30 wt % to 40 wt % or 40 wt % to 55 wt %. In one or more embodiments, the polyolefins may be amorphous polyolefins having a heat of fusion of less than 25 J / g or less than 15 J / g.In one or more embodiments, the polyolefins may be metallocene-catalyzed polyolefin polymers.

[0171] Commercial examples of acceptable polyolefins include Eastman's Aerafin TM 17. Eastman's Aerafin TM 180; Rextac manufactured by REXtac LLC TM Polymers, including Rextac TM E-63, E-65, 2760, 2815, 2730 and 2830; polymers manufactured by Evonik Industries include 408 and 708; and Eastman include E1060 and P1010.

[0172] Some examples of metallocene-catalyzed polymers include polyolefins such as polyethylene, polypropylene, and copolymers thereof. Exemplary polypropylene-based elastomers include those sold by ExxonMobil Chemical under the trade name VISTAMAXX TM Those sold by Idemitsu Kosan (Japan) under the trade name L-MODU TM Those sold by Dow Chemical Company under the trade name AFFINITY TM 、AFFINITY TM GA, INFUSE TM and ENGAGE TM Those sold; by ExxonMobil Chemical Company (Houston, Texas) under the trade name VISTAMAXX TM Those sold by Clariant under the trade name LlCOCENE TM The ones that are sold.

[0173] In one embodiment or in combination with any embodiment mentioned herein, the olefin polymer comprises a mixture of at least two different olefin polymers, such as a blend comprising an olefin homopolymer and an olefin copolymer, a blend comprising different olefin homopolymers of the same or different monomers, a blend comprising different olefin copolymers, and various combinations thereof. Useful olefin polymers also include, for example, modified, unmodified, grafted and ungrafted olefin polymers, unimodal olefin polymers, multimodal olefin polymers, and combinations thereof.

[0174] In one embodiment or in combination with any embodiment mentioned herein, these added polyolefins can increase the cohesive strength, adhesive properties, tack, low temperature flexibility, total crystallinity and / or temperature resistance of the adhesive composition of the present invention. In addition, due to the wide availability of the above-mentioned polyolefins, the addition of the above-mentioned polyolefins can reduce the production cost of the composition.

[0175] In certain embodiments, adhesive compositions can comprise propylene-ethylene copolymers of the present invention and metallocene-catalyzed polyethylene copolymers, such as ethylene-octene copolymers. In such embodiments, propylene-ethylene copolymers of the present invention can be used to replace the polyethylene in various types of adhesives (such as those for packaging applications).

[0176] In certain embodiments, the added polymers and / or polyolefins may be functionalized at the polymer chain ends and / or pendant positions within the polymer with groups including, but not limited to, silanes, anhydrides such as maleic anhydride, hydroxyls, ethoxyls, epoxies, siloxanes, amines, amine siloxanes, carboxyls, and acrylates.

[0177] The additional polymers and polyolefins that can be added to the adhesive composition of the present invention can be prepared by Ziegler-Natta catalysts, single-site catalysts (metallocenes), multiple single-site catalysts, non-metallocene heteroaryl catalysts, combinations thereof, or another polymerization method. The additional polymers can include amorphous structures, semi-crystalline structures, random structures, branched structures, linear structures, or combinations of block structures.

[0178] Any conventional polymerization synthesis method can prepare other polyolefin components.In one or more embodiments, one or more catalysts (usually metallocene catalysts or Ziegler-Natta catalysts) are used for the polymerization of olefin monomers or monomer mixtures.Polymerization methods include high pressure polymerization, slurry polymerization, gas polymerization, bulk polymerization, suspension polymerization, supercritical polymerization or solution phase polymerization or their combination.Catalyst can be in the form of homogeneous solution, supported catalyst or their combination.Polymerization can be carried out by continuous, semi-continuous or intermittent methods, and can include the use of chain transfer agents, scavengers or other such additives considered to be applicable.In one or more embodiments, a single polymerization catalyst is used to produce other polymers in a single or multiple polymerization zones.Metallocene (or heterogeneous) polymers are usually prepared using a variety of metallocene catalyst blends that obtain desired heterogeneous structures.

[0179] In one embodiment or in combination with any embodiment mentioned herein, the crystalline content of the added polymer or polyolefin can increase the cohesive strength of the adhesive composition. Typically, a formulation based on a metallocene polymerized semi-crystalline copolymer can eventually develop sufficient crystalline content over time to achieve good cohesive strength in the formulation.

[0180] In one embodiment or with any embodiment combination mentioned herein, adhesive composition can comprise at least 5 % by weight, 10 % by weight, 15 % by weight, 20 % by weight, 25 % by weight, 30 % by weight, 35 % by weight, 40 % by weight or 45 % by weight and / or be no more than at least one tackifier of 90 % by weight, 80 % by weight, 70 % by weight, 55 % by weight, 50 % by weight, 45 % by weight or 40 % by weight.In addition, adhesive can comprise at least one tackifier in 5 % by weight to 90 % by weight, 20 % by weight to 80 % by weight, 20 % by weight to 40 % by weight, 20 % by weight to 30 % by weight, 30 % by weight to 70 % by weight or 40 % by weight to 55 % by weight scope.Tackifier gives adhesive tack, and can also reduce the viscosity of adhesive.Lower viscosity can improve and apply flow characteristics, thereby allow easier processing, lower energy requirement and lower processing temperature.Lower viscosity also helps adhesive " thoroughly soaking through " or substantially evenly coating surface and infiltrating substrate. Tack is required in most adhesive formulations to allow for proper joining of articles prior to curing of the hot melt adhesive.The suitability and selection of a particular tackifier may depend on the specific type of olefin copolymer and additional polymer employed.

[0181] Suitable tackifiers may include, for example, alicyclic hydrocarbon resins, C5 hydrocarbon resins; C5 / C9 hydrocarbon resins; aromatic modified C5 resins; C9 hydrocarbon resins; pure monomer resins, such as copolymers of styrene with α-methylstyrene, vinyltoluene, p-methylstyrene, indene, methylindene, C5 resins and C9 resins; terpene resins; terpene phenolic resins; terpene styrene resins; rosin esters; modified rosin esters; liquid resins of fully or partially hydrogenated rosin; fully or partially hydrogenated rosin esters; fully or partially hydrogenated modified rosin resins; fully or partially hydrogenated rosin alcohols; fully or partially hydrogenated C5 resins; fully or partially hydrogenated C5 / C9 resins; fully or partially hydrogenated aromatic modified C5 resins; fully or partially hydrogenated C9 resins; fully or partially hydrogenated pure monomer resins; fully or partially hydrogenated C5 / alicyclic resins; fully or partially hydrogenated C5 / alicyclic / styrene / C9 resins; fully or partially hydrogenated alicyclic resins; and combinations thereof. Exemplary commercial hydrocarbon resins include Regalite TM Hydrocarbon resin (Eastman Chemical). In certain embodiments, the tackifier may include a functionalized tackifier.

[0182] In one embodiment or in combination with any embodiment mentioned herein, adhesive composition can comprise at least 1 % by weight, 2 % by weight, 5 % by weight, 8 % by weight or 10 % by weight and / or be no more than at least one processing oil of 40 % by weight, 30 % by weight, 25 % by weight, 20 % by weight or 15 % by weight. In addition, adhesive can comprise at least one processing oil in the scope of 2 % by weight to 40 % by weight, 5 % by weight to 30 % by weight, 8 % by weight to 25 % by weight or 10 % by weight to 20 % by weight. Processing oil can comprise for example mineral oil, naphthenic oil, paraffin oil, aromatic oil, castor oil, rapeseed oil, triglyceride oil or their combination. As those skilled in the art will appreciate, processing oil can also comprise the extender oil that is usually used in adhesive. If adhesive is used as pressure-sensitive adhesive to produce adhesive tape or label or to adhere nonwoven articles as adhesive, then it may be desirable to use oil in adhesive. In certain embodiments, adhesive can not comprise any processing oil.

[0183] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive composition can include at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, and / or no more than 40%, 35%, 34%, 33%, 32%, 31%, 30%, 29%, 28%, 27%, 26%, 25%, 24%, 23%, 22%, 21%, 20%, 19%, 18%, 17%, 16%, or 15% by weight of at least one wax. In addition, tackiness agent can comprise at least one wax in 0 % by weight to 15 % by weight, 1 % by weight to 40 % by weight, 5 % by weight to 30 % by weight, 8 % by weight to 25 % by weight, 10 % by weight to 20 % by weight, 1 % by weight to 25 % by weight, 1 % by weight to 20 % by weight, 1 % by weight to 15 % by weight, 1 % by weight to 10 % by weight or 1 % by weight to 5 % by weight scope.Wax is used to reduce the overall viscosity of tackiness agent, thereby allows its liquefaction and allows hot melt adhesive to be suitably applied or coated on the expected substrate.The type of wax and the compatibility of other components of melting point and adhesive composition control the open time and the solidification speed of tackiness agent.Open time is referred to as tackiness agent in the art and thoroughly soaks through and is bonded to the time amount of substrate after applying.Any conventional known wax that is suitable for preparing hot melt adhesive can be used for putting into practice the present invention.

[0184] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive composition may comprise at least 1 wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt% of a polyethylene wax, a polypropylene wax, a maleated polyolefin wax, or a combination of two or more thereof. Additionally or in the alternative, the adhesive composition may include no more than 40%, 35%, 34%, 33%, 32%, 31%, 30%, 29%, 28%, 27%, 26%, 25%, 24%, 23%, 22%, 21%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2% or 1% by weight of a polyethylene wax, a polypropylene wax, a maleated polyolefin wax, or a combination of two or more thereof.

[0185] Suitable waxes may include, for example, microcrystalline waxes, paraffin waxes, waxes produced by the Fischer-Tropsch process, functionalized waxes (maleated waxes, fumarated waxes or waxes with functional groups, etc.), polyolefin waxes, petroleum waxes, polypropylene waxes, polyethylene waxes, ethylene vinyl acetate waxes, and vegetable waxes. If the adhesive is used as a hot melt packaging adhesive, it may be desirable to use waxes in the adhesive.

[0186] Non-limiting examples of commercially available waxes suitable for use in the present invention include: H-1; AC available from Honeywell International Inc. TM -9, AC-596 and AC 810; EPOLENE available from Westlake Chemical TM N-15 and E-43; and POLYWAX from Baker Hughes Inc. TM 400, 850, 1000 and 3000. Other exemplary waxes include, but are not limited to, Clariant Licocene TM PE4201; Westlake EPOLENE TM C-10, EPOLENE TM C-17 and EPOLENE TM C-18; and Be Square Microcrystalline Wax TM 195.

[0187] As used herein, "functionalized" means that a component is prepared in the presence of functional groups incorporated into the component, or the component is contacted with functional groups and optionally with a catalyst, heat, initiator, or free radical source to incorporate, graft, bond, physically attach, and / or chemically attach all or a portion of the functional groups (such as maleic acid or maleic anhydride) into, graft, bond to, physically attach to, and / or chemically attach to a polymer.

[0188] Exemplary functionalized wax polymers useful as the functionalizing component include those modified with alcohols, acids, ketones, anhydrides, and the like. Commercial functionalized waxes include: maleated polypropylene available under the trade name MAPP 40 from Chusei; maleated metallocene waxes such as TP LICOCENE PP1602 available from Clariant; maleated polyethylene waxes and maleated polypropylene waxes available under the trade names EPOLENE C-16, EPOLENE C-18, EPOLENE E43 available from Westlake; EASTMAN G-3003 available from Eastman Chemical; maleated polypropylene wax LICOMONT AR 504 available from Clariant; graft functionalized polymers available under the trade names AMPLIFY EA 100 and AMPLIFY VA 200 available from Dow Chemical Co.; and CERAMER 1608, CERAMER 1251, CERAMER 67, and CERAMER 24 available from Baker Hughes. TM Maleated ethylene polymers. Available waxes also include polyethylene and polypropylene waxes having an Mw of 15,000 or less, preferably 3,000 to 10,000 and a crystallinity of 5 wt % or more, preferably 10 wt % or more, and having a functional group content of up to 10 wt %. Other functionalized polymers that can be used as functional components include AC 575P, AC 573P, AC X596A, AC X596P, A-CX597A, AC X597P, AC X950P, AC X1221, AC 395A, AC 395A, AC 1302P, AC 540, AC 54A, A-C629, AC 629A, AC 307, and A-C307A available from Honeywell International Inc.

[0189] In certain embodiments, the adhesive composition may not include wax. For example, the adhesive composition may include less than 10 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt%, or 1 wt% wax, such as, but not limited to, polyethylene wax and / or Fischer-Tropsch wax.

[0190] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition may include at least 0.1 wt %, 0.2 wt %, 0.5 wt %, 1 wt %, 2 wt % or 3 wt % and / or no more than 20 wt %, 10 wt %, 8 wt %, 5 wt %, 1 wt % or 0.5 wt % of at least one antioxidant. In addition, the adhesive composition may include at least one antioxidant in the range of 0.1 wt % to 20 wt %, 1 wt % to 10 wt %, 2 wt % to 8 wt % or 3 wt % to 5 wt %.

[0191] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition may include at least 0.5 wt %, 1 wt %, 2 wt % or 3 wt % and / or be no more than 20 wt %, 10 wt %, 8 wt % or 5 wt % at least one plasticizer. In addition, the adhesive may include at least one plasticizer in the range of 0.5 wt % to 20 wt %, 1 wt % to 10 wt %, 2 wt % to 8 wt % or 3 wt % to 5 wt %. Suitable plasticizers may include, for example, olefin oligomers, low molecular weight polyolefins such as liquid polybutene, polyisobutylene, mineral oil, dibutyl phthalate, dioctyl phthalate, chlorinated paraffin and plasticizers that do not contain phthalates. Commercial plasticizers may include, for example, Benzoflex TM Plasticizer (Eastman Chemical); Eastman 168 TM (Eastman Chemical); B10 (BASF); REGALREZ 1018 (Eastman Chemical); Calsol 5550 (Calumet Lubricants); Kaydol oil (Chevron); or ParaLux oil (Chevron).

[0192] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition may include at least 10 wt %, 20 wt %, 30 wt % or 40 wt % and / or no more than 90 wt %, 80 wt %, 70 wt % or 55 wt % of at least one filler. In addition, the adhesive may include at least one filler in the range of 1 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 55 wt %. Suitable fillers may include, for example, carbon black, calcium carbonate, clay, titanium oxide, zinc oxide or a combination thereof.

[0193] Adhesive composition can be produced using conventional techniques and equipment. For example, the components of adhesive composition can be blended in a mixer such as a sigma blade mixer, a plastic meter, a Brabender mixer, a twin screw extruder or a blender in a jar (pint jar). In one embodiment or in combination with any embodiment mentioned herein, adhesive can be formed into a desired form, such as adhesive tape or sheet material, by suitable technology, including for example extrusion, compression molding, calendering or roller coating technology (for example, gravure, reverse roller etc.), curtain coating, slot die coating or spraying.

[0194] In addition, the adhesive composition can be applied to substrates by a solvent casting process or by using conventional hot melt adhesive application equipment known in the art to melt the adhesive. Suitable substrates may include, for example, nonwovens, textile fabrics, paper, glass, plastics, films (polyethylene, polypropylene, polyester, etc.) and metals. Typically, about 0.1 g / m 2 Up to 100g / m 2 , about 0.1g / m 2 About 150g / m 2 or about 1g / m 2 About 1000g / m 2 The adhesive composition is applied to a substrate.

[0195] According to one or more embodiments, the hot melt adhesive composition may have a Brookfield viscosity of at least 100 cps, 300 cps, 500 cps, 750 cps, or 1,000 cps and / or no greater than 60,000 cps, 40,000 cps, 30,000 cps, 20,000 cps, 10,000 cps, 5,000 cps, 4,000 cps, 3,000 cps, or 2,500 cps at 177°C as measured according to ASTM D3236. In addition, the hot melt adhesive may have a viscosity of 100 cps to 60,000 cps, 300 cps to 10,000 cps, 500 cps to 5,000 cps, 750 cps to 2,500 cps, 400 cps to 3,000 cps, 500 cps to 1,000 cps, 500 cps to 5,000 cps, 500 cps to 10,000 cps, 50 ...400 cps to 1,000 cps, 400 cps to 5,000 cps, 400 cps to 2,500 cps, 400 cps to 3,000 cps, 400 cps to 1,000 cps, 400 cps to 5,000 cps, 400 cps to 1,000 cps, 400 cps to 2,500 cps, 400 cps to 3,000 cps, 400 cps to 1,000 cps, 400 cps to 2,500 cps, 400 cps to 3,000 cps, 400 cps to Brookfield viscosity in the range of cps to 15,000cps, 500cps to 20,000cps, 1,000cps to 5,000cps, 1,000cps to 10,000cps, 1,000cps to 15,000cps, 1,000cps to 20,000cps, 1,000cps to 40,000cps, 1,000cps to 60,000cps.

[0196] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 190°C of at least 100 cps, 500 cps, 1,000 cps, 2,000 cps, 3,000 cps, 4,000 cps, 5,000 cps, 6,000 cps, 7,000 cps, 8,000 cps or 9,000 cps and / or no greater than 60,000 cps, 50,000 cps, 40,000 cps, 30,000 cps, 20,000 cps, 15,000 cps or 10,000 cps as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 190°C ranging from 100 cps to 60,000 cps, 500 cps to 30,000 cps, 1,000 cps to 40,000 cps, 1,000 cps to 10,000 cps, 2,000 cps to 20,000 cps, 2,000 cps to 10,000 cps, 2,000 cps to 15,000 cps, 3,000 cps to 15,000 cps, 2,500 cps to 25,000 cps, or 2,000 cps to 30,000 cps.

[0197] In addition, in various embodiments, the hot melt adhesive composition can have a 90 degree peel strength (T-peel) of at least 1 g / mm, 2 g / mm, 5 g / mm, 10 g / mm, or 15 g / mm and / or no more than 50 g / mm, 40 g / mm, 35 g / mm, 30 g / mm, or 25 g / mm, as measured according to ASTM D 903. In addition, the hot melt adhesive can have a peel strength in the range of 1 g / mm to 50 g / mm, 2 g / mm to 40 g / mm, 5 g / mm to 35 g / mm, 10 g / mm to 30 g / mm, or 15 g / mm to 25 g / mm, as measured according to ASTM D 903. Additionally or alternatively, the hot melt adhesive may have a 90 degree peel strength of at least 0.05 lbf / inch, 0.1 lbf / inch, 0.2 lbf / inch, or 0.5 lbf / inch and / or no greater than 20 lbf / inch, 10 lbf / inch, 5 lbf / inch, or 1 lbf / inch, as measured according to ASTM D903.

[0198] According to various embodiments, the adhesive composition containing the copolymer of the present invention may have a wide operating window and may have an application window of 80° C. to 230° C. Such a wide operating window may be demonstrated by the peel strength of the adhesive at different temperatures.

[0199] In one embodiment or in combination with any embodiment mentioned herein, the hot melt adhesive composition can have a holding power of at least 0.1 hour, 0.5 hour, or 1 hour and / or no more than 50,000 hours, 10,000 hours, 5,000 hours, 1,000 hours, 500 hours, 100 hours, 50 hours, 20 hours, 10 hours, 7 hours, or 4 hours at 50° C., as measured according to ASTM D3654. In addition, the hot melt adhesive can have a holding power in the range of 0.1 hour to 10 hours, 0.5 hour to 7 hours, or 1 hour to 4 hours at 50° C., as measured according to ASTM D3654.

[0200] In other embodiments, the hot melt adhesive composition may exhibit a holding force of at least 5 minutes, 15 minutes, 20 minutes or 25 minutes and / or no more than 150 minutes at 60°C. Additionally or alternatively, the hot melt adhesive may exhibit a holding force of at least 400 minutes, 600 minutes, 800 minutes or 1,000 minutes at 50°C. The holding force at 50°C and 60°C may be measured in the following manner: the glued carton substrate is stabilized overnight at a room temperature of typically 20°C to 23°C, and then the substrate is suspended in a shear group oven in a peeling mode. A weight is then suspended under the glued substrate. The time of weight reduction due to failure of each sample is recorded.

[0201] The hot melt adhesive composition may exhibit a shear adhesion failure temperature ("SAFT") of at least 2°C, 3°C, 30°C, 50°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 135°C and / or no greater than 200°C, 160°C, 155°C, 150°C, 140°C, 135°C, 134°C, 133°C, 130°C or 135°C, as measured according to ASTM D4498. In addition, the hot melt adhesive may have a SAFT in the range of 2°C to 200°C, 30°C to 200°C, 50°C to 150°C, 75°C to 125°C, 130°C to 160°C, 130°C to 155°C, 130°C to 150°C, 130°C to 145°C, 135°C to 155°C, 135°C to 150°C, 140°C to 160°C, 140°C to 155°C, 140°C to 150°C, 145°C to 160°C, 145°C to 155°C, or 145°C to 150°C, as measured according to ASTM D4498.

[0202] In one embodiment or in combination with any embodiment mentioned herein, the hot melt adhesive composition may exhibit a high temperature performance fiber tear ("HTFT") of at least 50%, 65%, 70%, 75%, 80%, 85%, 90% or 95% at 60°C. The HTFT test consists of manually tearing the glued corrugated cardboard (carton) substrate by hand under the conditions of 60°C. Before tearing, the glued carton substrate must be stable for 4 hours plus or minus 5 minutes under the conditions of 60°C. If 80% of the fibers of the substrate are broken, it is considered that the test is passed, so it is considered that the hot melt adhesive performs well. For some applications, if 50% of the fibers of the substrate are broken, it is considered that the test is passed and it is considered that the adhesive performs well at 60°C.

[0203] In one embodiment or in combination with any embodiment mentioned herein, the adhesive containing the copolymer of the present invention does not show significant color change when subjected to storage conditions at high temperatures for a long period of time. Before any aging occurs due to storage, the adhesive may have an initial Gardner color of less than 18, 15, 10, 8, 5, 4, 3, 2 or 1, as measured according to ASTM D1544. After heat aging at 177°C for at least 96 hours, the adhesive may show a final Gardner color of less than 18, 15, 10, 7, 5, 3, 2 or 1, as measured according to ASTM D1544. Therefore, the adhesive can maintain a desired color even after long-term storage and exposure.

[0204] In one embodiment or in combination with any embodiment mentioned herein, propylene-ethylene copolymer of the present invention can be used in adhesive composition as previously described in the present disclosure.Especially, propylene-ethylene copolymer of the present invention can be used to produce hot melt adhesive with wide process window and high peel strength to laminate (such as but not limited to instrument panel assembly for automotive interior decoration).In various embodiments of the present invention, adhesive formulation is used as hot melt adhesive and comprises at least one copolymer of the present invention and at least one tackifier resin.Optionally, hot melt adhesive can also comprise wax, optional oil and / or antioxidant.In a specific embodiment, hot melt adhesive comprises copolymer of the present invention of about 40 % by weight to about 85 % by weight and tackifier resin of about 15 % by weight to about 45 % by weight.In another embodiment, hot melt adhesive composition does not comprise tackifier resin.

[0205] One embodiment of the present invention relates to a vehicle having a vehicle interior material (preferably an automobile interior material) comprising a skin material (preferably a polyolefin-based substrate) to which a hot-melt composition is applied. Examples of vehicles according to the present invention include, but are not particularly limited to, vehicles such as motor vehicles (cars), motor bicycles (motorcycles), buses, and trams. In this specification, although the term "automobile interior material" is used in some sentences, the term can also be understood to mean an interior material for vehicles other than automobiles, as long as the hot-melt composition of the present invention can be applied.

[0206] The compositions of the present invention can be used to form bonds to produce laminates and multilayer laminates.The terms "laminate" and "multilayer laminate" are used interchangeably.

[0207] The present composition according to one or more embodiments of the present invention can be bonded to various adherends, and these adherends include but are not limited to: cellulose polymer materials such as paper, cotton, flax, cloth and wood board; synthetic polymer materials, including polyolefin resins such as polypropylene and polyethylene, styrene resins such as polystyrene, styrene-butadiene block copolymers (SBS resins), styrene-acrylonitrile copolymers (AS resins), acrylonitrile-ethylene / propylene styrene copolymers (AES resins) and acrylonitrile-butadiene-styrene copolymers (ABS resins), polycarbonate resins (PC resins), (methyl) acrylic resins, polyester resins, polyamide resins such as nylon and polyurethane, phenolic resins and epoxy resins. The material for adherend can be a mixture or combination of two or more different materials. When forming laminate by bonding two different adherends via the adhesive layer comprising propylene-ethylene polymer of the present invention or hot-melt adhesive, the materials of two kinds of adherends can be identical or different from each other.

[0208] Laminates comprising the polymer or composition of the present invention can be suitably used in applications where covering materials and shaped articles are used as adherends, such as automotive interior materials (e.g., ceiling materials for automotive interior parts, door components for automotive interior parts, instrument panel components for automotive interior parts, instrument panels), components for home appliances (e.g., housings of personal computers, frames of flat-panel televisions), and housing materials (e.g., interior wall panels, decorative films, etc.).

[0209] Covering material refers to a material that has been formed into a film, sheet, foam, or any type of nonwoven or woven material. Examples include decorative polymer sheets made of polyvinyl chloride, various polyolefins or ABS, thermoplastic polyolefin compounds (TPO) such as polypropylene blended with uncrosslinked EPDM rubber and / or polyethylene, polyester nonwoven fabrics, fleece knits, fabrics, polyurethane artificial leather, and polyolefin foams formed primarily of polypropylene, polyethylene, polybutylene, or copolymers of these olefins. Examples of shaped articles include injection molded articles of various polymer materials such as ABS, PC / ABS, polyolefins, glass fiber reinforced polyolefins, and glass fiber reinforced nylons; and wooden shaped articles and wooden boards prepared by encapsulating materials such as wood chips or wood powder in thermosetting resins or polyolefin resins by hot compression molding.

[0210] When a multilayer laminate is prepared by bonding a covering material such as a decorative sheet to a shaped article used as a base material via an adhesive layer containing the propylene-ethylene polymer of the present invention or a hot melt adhesive, various forming methods such as thermal lamination, vacuum forming, vacuum pressure forming, hot pressing, hot rolling and hot stamping can be used. Among the shaped articles made of the above materials, the curved shaped article means a shaped article having a planar arc surface as a surface to be bonded to the covering material. Such shaped articles are used to form a shape skeleton in the housing of an automobile interior or a household appliance.

[0211] In other embodiments of the present invention, adhesive composition formulations are provided. Each of the subsequent embodiments contains the propylene-ethylene copolymer of the present invention as described previously in this disclosure.

[0212] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising at least one propylene-ethylene copolymer, wherein the propylene-ethylene copolymer comprises ethylene and propylene; wherein the amount of propylene is in the range of about 89 wt% to about 95 wt%; wherein the ethylene-propylene copolymer has a Ring and Ball softening point of about 135°C to 160°C, and wherein the ethylene-propylene copolymer has a triad tacticity of about 50% to about 70%; wherein the composition comprises:

[0213] (a) 5 to 100 wt% of the at least one propylene-ethylene copolymer;

[0214] (b) 0% to 55% by weight of at least one second polymer;

[0215] (c) no more than 70% by weight of at least one tackifier;

[0216] (d) not more than 20% by weight of process oil; and

[0217] (e) not more than 35% by weight of at least one wax.

[0218] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition, wherein the composition comprises:

[0219] (a) 5 to 100 wt% of the at least one propylene-ethylene copolymer;

[0220] (b) 0% to 50% by weight of at least one second polymer;

[0221] (c) no more than 70% by weight of at least one tackifier;

[0222] (d) not more than 20% by weight of process oil; and

[0223] (e) not more than 35% by weight of at least one wax.

[0224] These adhesive compositions may have a Brookfield viscosity ranging from about 2,000 cP to about 20,000 cP at 177°C; and / or a shear adhesion failure temperature of at least about 135°C; and / or a thermal creep length of 5 mm or less at 110°C; and / or a thermal creep length of 5 mm or less at 120°C.

[0225] These adhesive compositions may have a Brookfield viscosity in the range of about 2,000 cP to about 20,000 cP at 190°C; and / or a shear adhesion failure temperature of at least about 135°C; and / or a thermal creep length of 5 mm or less at 110°C; and / or a thermal creep length of 5 mm or less at 120°C.

[0226] In one embodiment or in combination with any embodiment mentioned herein, the adhesive compositions may have a composition having a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 177°C; and / or a shear adhesion failure temperature of at least about 135°C; and / or a thermal creep length of 5 mm or less at a temperature at least 10°C higher than the temperature at which an equivalent composition not comprising the at least one propylene-ethylene copolymer has a thermal creep length of 5 mm or less.

[0227] In one embodiment or in combination with any embodiment mentioned herein, the adhesive compositions may have a composition having a Brookfield viscosity in the range of about 2,000 to about 20,000 cP at 190°C; and / or a shear adhesion failure temperature of at least about 135°C; and / or a thermal creep length of 5 mm or less at a temperature at least 10°C higher than the temperature at which an equivalent composition not comprising the at least one propylene-ethylene copolymer has a thermal creep length of 5 mm or less.

[0228] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0229] (a) 10 to 70 wt% of the at least one propylene-ethylene copolymer;

[0230] (b) 5 to 55 weight percent of at least one second polymer;

[0231] (c) no more than 70% by weight of at least one tackifier;

[0232] (d) not more than 20% by weight of process oil; and

[0233] (e) not more than 20% by weight of at least one wax

[0234] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0235] (a) 5 to 95 weight percent of the at least one propylene-ethylene copolymer;

[0236] (b) 5 to 90 weight percent of the at least one second polymer;

[0237] (c) no more than 70% by weight of at least one tackifier;

[0238] (d) not more than 20% by weight of process oil; and

[0239] (e) up to 20% by weight of at least one wax.

[0240] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0241] (a) 30 to 80 wt% of the at least one propylene-ethylene copolymer;

[0242] (b) 1 to 45 weight percent of the at least one second polymer;

[0243] (c) no more than 70% by weight of at least one tackifier;

[0244] (d) not more than 20% by weight of process oil; and

[0245] (e) up to 20% by weight of at least one wax.

[0246] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0247] a) 35 to 85 wt.% of the at least one propylene-ethylene copolymer;

[0248] (b) 0% to 45% by weight of the at least one second polymer;

[0249] (c) 5 to 35 weight percent of at least one tackifier;

[0250] (d) no more than 33% by weight of at least one wax; and

[0251] (e) up to 17% by weight of at least one polypropylene wax.

[0252] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0253] (a) 35 to 85 weight percent of the at least one propylene-ethylene copolymer;

[0254] (b) 0% to 45% by weight of the at least one second polymer;

[0255] (c) 5 to 35 weight percent of at least one tackifier;

[0256] (d) no more than 26% by weight of at least one polyethylene wax; and

[0257] (e) up to 7% by weight of at least one polypropylene wax.

[0258] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided an adhesive composition comprising:

[0259] (a) 50 to 95 weight percent of the at least one propylene-ethylene copolymer;

[0260] (b) 0% to 55% by weight of at least one second polymer;

[0261] (c) 5 to 35 weight percent of at least one tackifier; and

[0262] (d) 0 to 15 wt. % of at least one wax.

[0263] In any of these adhesive compositions, the composition may further comprise at least one second polymer selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers (including ethylene-propylene-butene terpolymers), propylene and linear or branched C4-C4 polymers. 10 Copolymers produced from α-olefin monomers, consisting of ethylene and linear or branched C4-C 10 Copolymers produced from α-olefin monomers, functionalized polyolefins, isoprene-based block copolymers; butadiene-based block copolymers; hydrogenated block copolymers; styrene-ethylene / butylene-styrene block copolymers (SEBS); styrene-isoprene-styrene block copolymers (SIS); styrene-ethylene / propylene-styrene (SEPS); ethylene vinyl acetate copolymers; polyesters; polyester-based copolymers; chloroprene rubber; urethanes; acrylic acid; polyacrylates; acrylate copolymers, such as but not limited to ethylene acrylic acid copolymers, ethylene n-butyl acrylate copolymers and ethylene methyl acrylate copolymers; polyetheretherketones; polyamides; styrene block copolymers; hydrogenated styrene block copolymers; random styrene copolymers; ethylene-propylene rubber; ethylene vinyl acetate copolymers; butyl rubber; styrene-butadiene rubber; nitrile rubber; natural rubber; polyisoprene; polyisobutylene; and polyvinyl acetate.

[0264] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided a method of preparing an adhesive composition, the method comprising mixing:

[0265] (a) 5 to 100 wt% of the at least one propylene-ethylene copolymer; wherein propylene

[0266] - an ethylene copolymer comprising ethylene and propylene; wherein the amount of propylene is in the range of about 89 wt % to about 95 wt %; wherein the ethylene-propylene copolymer has a Ring and Ball softening point of about 135° C. to 160° C., and wherein the ethylene-propylene copolymer has about 50% to about 70%

[0267] The triadic stereoregularity of

[0268] (b) 0% to 55% by weight of at least one second polymer;

[0269] (c) no more than 70% by weight of at least one tackifier;

[0270] (d) not more than 20% by weight of process oil; and

[0271] (e) not more than 35% by weight of at least one wax.

[0272] In this method, the adhesive composition can be used to bond to a substrate and subsequently laminated to another substrate.

[0273] In one embodiment or in combination with any of the embodiments mentioned herein, there is provided a method for preparing an automotive assembly component, the method comprising:

[0274] (a) applying the adhesive composition to a surface of at least one layer of a substrate, and

[0275] (b) A laminate is formed by bringing the surfaces to be adhered into contact with each other.

[0276] Various articles can be produced using the adhesive composition. An article comprising the adhesive composition is provided, wherein the article is selected from the group consisting of adhesives, sealants, caulks, roofing membranes, waterproofing membranes, compounds and pads, carpets, laminates, laminated products, tapes, labels, adhesives, polymer blends, wire coatings, molded products, heat seal coatings, disposable sanitary products, insulating glass (IG) units, bridge deck systems, modified asphalt, modified asphalt, electronic housings, waterproof membranes, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, glass fiber reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles (cars), motor bicycles (motorcycles), public Automobiles and railcars, trucks, automotive molded parts, automotive extruded parts, apparel articles, rubber additives / processing aids and fibers; wherein adhesives include: packaging adhesives, food contact grade adhesives, indirect food contact packaging adhesives, product assembly adhesives, woodworking adhesives, edge banding adhesives, profile packaging adhesives, flooring adhesives, automotive assembly adhesives, structural adhesives, flexible laminating adhesives, rigid laminating adhesives, flexible film adhesives, flexible packaging adhesives, water-activated adhesives, home improvement adhesives, industrial adhesives, construction adhesives, furniture adhesives, mattress adhesives, pressure sensitive adhesives (PSA), PSA tapes, PSA labels, PSA protective films, self-adhesive films, laminating adhesives, flexible packaging adhesives, heat sealing adhesives, industrial adhesives, sanitary nonwoven construction adhesives, sanitary core integrity adhesives and sanitary elastic attachment adhesives.

[0277] The present invention may be further illustrated by the following examples of its embodiments, although it should be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless otherwise specifically stated.

[0278] Example

[0279] Polymerization of heat-resistant propylene-ethylene copolymers

[0280] Various inventive propylene-ethylene copolymers are produced having specific propylene content, desired triad tacticity (mm%) (ie, reflecting isotactic structure), and high ring and ball softening point (RBSP). The propylene-ethylene copolymers are produced according to the following polymerization process.

[0281] Reactants propylene, ethylene and hydrogen are fed to a 5 gallon continuous stirred tank reactor (CSTR) along with diluent, external donor and catalyst at the ratio, flow rate and temperature provided in Table 2A, Table 2B and Table 2C for each sample produced. The inventive samples and comparative samples (i.e., the comparative samples produced) in Table 3A and Table 3B are prepared with the 3rd generation (benzoate) catalyst and alkoxysilane as the above-mentioned external electron donor, and the inventive samples and comparative samples in Table 3C are prepared with the 5th and 6th generation catalysts in the presence and absence of the above-mentioned external electron donor. The reactor is operated at a pressure in the range of 790psi to 850psi. In addition, a hot oil system provides tracking for the reactor jacket. A dip tube takes the product out of the reactor, and a back pressure regulator (pressurized with helium) maintains pressure control of the reactor.

[0282] The diluent is then removed from the copolymer from the discharge tank and the residual catalyst is then deactivated using steam and nitrogen in a hot oil jacketed exchanger. The molten copolymer is then collected from the bottom of the deactivator and pumped to a final product collection tank.

[0283] The resulting copolymers in Table 1 were prepared as described above using the conditions listed in Table 2A, Table 2B, and Table 2C. The properties of the copolymers obtained from the given conditions in Table 2A, Table 2B, and Table 2C are provided in Table 3A, Table 3B, and Table 3C.

[0284] The inventive examples in Table 2A, Table 3A, Table 2B and Table 3B were produced using the above-described Generation 3 or Generation 4 ZN catalyst system and an external electron donor. Compared to Comparative Examples 1-6, the combination of a donor ratio of less than about 1:1 and an ethylene flow rate of less than 40 g / h unexpectedly produced a Ring and Ball softening point above 135°C and a needle penetration force typically less than about 21 and a tensile strength typically above about 2.5 MPa.

[0285] As shown in Tables 3A and 3B, the addition of an external donor generally increases hardness, as indicated by a decrease in needle penetration force and an increase in copolymer viscosity. In addition, a decrease in ethylene flow rate results in a copolymer having a high propylene to ethylene comonomer ratio, thereby increasing RBSP and hardness, as indicated by a decrease in needle penetration force. Compared to Comparative Example 6 (Example C1 of U.S. Patent 942,859 from Eastman Chemical Company), the inventive examples were produced at a lower relative ethylene flow rate (meaning a lower relative ethylene flow rate at a comparable propylene flow rate) and using an external donor. As shown in Table 3, it was observed that the copolymer of Inventive Example 1 had an increase in Ring and Ball softening point (RBSP) of about 20% and a decrease in needle penetration force of about 95% compared to Comparative Example 6.

[0286] Unexpectedly, the polymers of the present invention having a low ethylene content of about 2 wt% to about 11 wt% and an experimental stereoregularity content (mm% measured by proton NMR) of about 50 wt% to about 70 wt% have both high RBSP (heat resistance) and high stretchability. In addition, the polymers of the present invention have a surprisingly wide range of viscosities of about 2000 cP to about 50000 cP at 190°C.

[0287] The inventive copolymers and comparative samples prepared under the conditions provided in Table 2A, Table 2B, and Table 2C were tested to verify the properties and characteristics of the copolymers. Unless otherwise stated, the described test methods were used to test various properties.

[0288] Techniques for determining ethylene and propylene composition by NMR can be found in Macromolecules, 2000, Vol. 33, pp. 1157-1162 (Wang et al.), and formulas for measuring triad tacticity can be found in U.S. Pat. No. 5,504,172 and in Tsutsui et al. (Polymer, 1989, Vol. 30, pp. 1350-1356), all of which are incorporated by reference in their entirety.

[0289] The sample was prepared by adding 0.4g polyolefin sample and 100mg Cr(acac)3 to a 4-dram vial, followed by adding 0.5mL o-dichlorobenzene-d4 and 3.5mL trichlorobenzene (non-deuterated). The resulting solution was magnetically stirred at 120°C until the copolymer was observed to be completely dissolved by visual inspection. Dissolution was usually completed within 1 hour. The 10mm NMR tube was warmed to 80°C. While wearing heat-resistant gloves, the warm solution was poured into the 10mm NMR tube until the sample height was about 4.5cm-5cm. The tube was then capped with a push-on cap. It is important to transfer the solution to the NMR tube while the solution is still warm so that it does not solidify before the transfer is completed. The spectrum was analyzed using MNova software. After Fourier transform was applied to the FID data, the spectrum was phased and the baseline was corrected, and calculated as described in the references given. It was determined that the standard deviation of PP% was 0.7, and the standard deviation of mm% was 0.3. The standard deviation of PP% was determined to be 0.7, and the standard deviation of mm% was determined to be 0.3.

[0290] The triad tacticity of a polymer is the relative tacticity of a sequence of three adjacent propylene units (a chain consisting of head-to-tail bonds), expressed as a binary combination of meso (m) and racemic (r) sequences. The triad tacticity, expressed here as "mm %", is determined by 13C nuclear magnetic resonance (NMR) and the following formula:

[0291]

[0292] Where PPP(mm), PPP(mr) and PPP(rr) represent the peak areas originating from the orientation of the methyl groups on the propylene sequence relative to the next corresponding methyl group of the propylene sequence, as shown in the following chemical shifts:

[0293] ·PPP(mm)=21.3ppm-22.0ppm;

[0294] ·PPP(mr)=20.6ppm-21.3ppm;

[0295] ·PPP(rr)=18.0ppm-22.5ppm.

[0296]

[0297] The triad tacticity of polypropylene is the relative tacticity of a sequence of three adjacent propylene units.

[0298] For comparison purposes, Table 3D provides the properties of various commercially available copolymers ("CACs") and commercial waxes.

[0299]

[0300]

[0301]

[0302]

[0303]

[0304]

[0305]

[0306] As shown in Table 3D, there are many commercially available copolymers on the market that have softening points that overlap with the copolymers of the present invention; however, Figure 1 As shown in Table 3D, these commercially available copolymers exhibit one or more defects that limit their use in high heat resistance applications. In addition, to improve the heat resistance characteristics of the adhesive, commercially available highly crystalline low molecular weight waxes with high crystallinity, such as those described in Table 3D, can be added. As shown in Table 3D and Figure 1 As shown in , although these commercial waxes can exhibit desirable softening points, they are very brittle (as indicated by the heat of crystallization). Therefore, due to their brittleness, there are some general problems in blending polyolefins with these waxes. Therefore, the use of these waxes may adversely affect the viscosity and cohesive strength of the resulting adhesive.

[0307] like Figure 1 As shown, the copolymers of the present invention of Tables 3A-3C have superior crystallinity and softening points relative to the commercial copolymers and waxes of Table 3D.

[0308] Experimental Procedures for Hot Melt Compositions, Laminates, and Bond Formation and Testing

[0309] Table 4A—Substrate

[0310]

[0311] Table 4B - Materials

[0312]

[0313] Preparation of hot melt adhesive compositions

[0314] Preheat the heating block to 180°C. Weigh the polymer, wax, resin and antioxidant into a pint aluminum container. The container is then placed in a heating mantle. After the mixture shows signs of melting, insert a stirrer and mix at about 150 rpm until it is homogeneous. Pour the adhesive onto the silicon-coated release paper and cool to room temperature.

[0315] Viscosity measurement of hot melt adhesives

[0316] Using a Thermosel TM The viscosity is measured using a Brookfield DV2 Textra viscometer with a spindle No. 27, according to an internal method that meets ASTM D-3236. 10.5 grams of adhesive are placed in a Brookfield tube, and the sample is heated to this temperature (if not melted) for 10 minutes. The sample is then balanced at each test temperature for 20 minutes under shear. The spindle rpm is adjusted to maximize the motor %, and no adjustment is made in the last 20 minutes of the shear equilibrium time. Values ​​are reported in centipoise (cP). Read the viscosity readings from low temperature to high temperature.

[0317] Adhesive Ring and Ball Softening Point (RBSP)

[0318] Adhesive ring and ball softening point is measured using a Herzog ring and ball softening point apparatus according to ASTM method E-28. The formulated adhesive is poured into a brass ring and allowed to cool overnight or for more than 16 hours. The sample is trimmed flat before testing. The silicone oil is heated at 5°C / min until the ball passes through the softened sample and the temperature is measured at this time. The reported value is the average of two readings.

[0319] Adhesive open time measurement

[0320] The open time was determined in the laboratory using an in-house method based on ASTM D4497-10 "Determining the open time of hot melt adhesives". The molten adhesive (180°C) was applied to kraft paper as a film of 127μm or 635μm (5 mils or 25 mils) using a hot scraping rod. The final film thickness was 3 mils-5 mils (0.1mm) or 20 mils-25 mils (0.5mm). The paper strips were pressed into the film at specific intervals (depending on the open time) using a 1kg weight block. 30 minutes after the last strip was applied, a 90-degree peel was performed by hand to determine which of the applied paper strips could be removed without pulling out the paper fibers (50% fiber tear). The time the strip was applied was recorded and the open time was calculated.

[0321] Preparation of polymer samples for tensile strength measurements

[0322] Tensile Strength Sample Preparation:

[0323] Film samples for tensile testing were prepared using a Carver tablet press. 20 grams of molten samples were placed in a 5-inch × 5-inch (137mm × 137mm) square aluminum mold frame with a thickness of 1mm. The sample was then sandwiched between a silicone-coated PET film, a release paper, and a metal plate, and then heated in a Carver tablet press without applying pressure. The sample was kept at 177°C to 188°C for 12 minutes, then a 6000PSI pressure was applied for 5 seconds and released, then the pressure was increased to 12000PSI and released again. Finally, 18000PSI pressure was applied and held for 2 minutes. The sample was then taken out of the tablet press and quickly transferred from the hot metal plate to a set of room temperature plates, which had a 10kg weight block on top to act as a heat sink. After a cooling time of 8 minutes, the blocks and metal plates were removed. The resulting 137 mm x 137 mm x 1 mm film was stored in a temperature and humidity controlled room (25°C, 50% RH) for 24 hours and then cut using a dumbbell cutter based on Die C of ASTM-D412.

[0324] Polymer tensile strength measurement

[0325] Tensile test:

[0326] Tensile strength and elongation at break were measured at 20 in / min (51 cm / min) according to the procedure described in ASTM D412 (die C). All tests were conducted in a controlled temperature and humidity (CTH) room at 25°C, 50% RH. The tensile strength at break was calculated by dividing the magnitude of the breaking force by the cross-sectional area of ​​the unstrained sample. The elongation at break was calculated by recording the extended break distance and was standardized by the original gauge length of 62.5 mm in the tensile fixture.

[0327] Melt Viscosity of Polyolefins

[0328] Melt viscosity of polyolefin polymers was measured at 190°C using a No. 27 spindle and a Brookfield RVDVI+ Brookfield RVDVI+ viscometer.

[0329] Performance Measurement

[0330] 1. Lamination of TPO foil and PP or ABS substrate

[0331] 1.1TPO-1 and PP or ABS

[0332] The adhesive and square film applicator in an aluminum pan (2 inch frame and 5 mil-50 mil gap) were heated in a 180°C oven for at least 30 minutes. The hot film applicator from the oven was placed on a TPO-1 sheet (approximately 9" x 5") and the molten adhesive was immediately poured into the film applicator. A 5 mil thick film of adhesive was then knife coated on the TPO-1 foil. After cooling, the coated foil was cut into 1.0 inch or larger widths for bonding to PP or ABS substrates.

[0333] The above TPO-1 foil with pre-coated adhesive was placed in an oven at 175°C with the adhesive layer facing up, and then a PP or ABS substrate with a size of 4"×1" and a thickness of 1 / 8" was placed on the coated TPO-1, followed by a 1 Kg weight. After closing the oven door for 2 minutes, the TPO-1 / PP or TPO-1 / ABS laminate was taken out of the oven and cooled to room temperature.

[0334] 1.2TPO-2 and PP

[0335] After introducing the adhesive melted at 180°C into a 2-inch square applicator with a 5-mil gap, an adhesive film of 2" width and about 10" length is knife-coated on the silicon paper. The silicon paper is cut into sizes of 2" long and 1" wide or larger, with the adhesive film on one end of the paper. The TPO-2 foil is cut into strips of about 5.5" long and 1" wide. Next, assemble from bottom to top in the following order: film on silicon paper, TPO-2 (contact layer facing down, decorative layer facing up), and weights, and then place on a hot plate with a surface temperature of ~180°C. After 15 seconds, the assembly is removed from the hot plate and cooled. The silicon paper is carefully removed to obtain an adhesive film coated on the TPO-2 foil with a coating weight of 60gsm-80gsm (grams per square meter).

[0336] The adhesive pre-coated TPO-2 foil was placed under an IR heater (Chromalox CPL-0612) for 25 seconds so that the adhesive surface reached a temperature of 140°C or higher. A PP substrate (4" x 1" x 1 / 8" size) was immediately placed on top of the adhesive. The PP / TPO-2 laminate was removed from the IR heating zone and a 2 Kg weight was applied.

[0337] 2. Shear Adhesion Failure Temperature (SAFT)

[0338] 2.1 PP and PP, 1kg SAFT

[0339] Shear Adhesion Failure Temperature (SAFT) was tested using two PP substrates (size 2" x 1") bonded with an adhesive. The adhesive was melted at 180°C-200°C for at least 20 minutes and then applied to one surface of the PP substrate using a laboratory spatula. Another PP substrate was immediately placed on top of the adhesive with gentle pressure to ensure a 1" x 1" bond area. A 1 Kg weight was placed on the bonded area for at least one hour. The adhesive thickness was 0.5 mm-0.7 mm. After cooling, excess adhesive was removed with a knife.

[0340] SAFT temperature measurements were performed in accordance with ASTM D4498-07 "Standard Test Method for Heat-Fail Temperature in Shear of hot Melt Adhesives". After conditioning at room temperature for at least 24 hours, the samples were placed in a programmable oven equipped with a Cheminstruments 30 group tester (West Chester Township, OH). The static load was 1 Kg. The heating program was set to run from 20°C to 150°C at a ramp rate of 0.5°C / min. The program records the time to bond failure (weight loss) and converts it to bond failure temperature. A total of five samples were tested and the average value reported.

[0341] 2.2 Birch Timber and Birch Timber, 500g SAFT

[0342] The procedure is the same as for PP / PP bonding, except that birch wood / birch wood substrates are used. The measurements are performed with a static load of 500 g.

[0343] 2.3 Kraft paper and kraft paper, 500g (packaging SAFT)

[0344] SAFT values ​​were obtained following in-house procedures for sample preparation and ASTM D4498-07 "Standard Test Method for Heat-Fail Temperature in Shear of hot Melt Adhesives" for temperature measurements. Two sheets of approximately 6" wide x 14" long kraft paper were placed on the work surface with the inside of the kraft roll facing up. An 8" wide x 14" long bonding template with a 1" wide x 12" long opening was placed on top of one sheet of kraft paper and the template was secured in place. The adhesive was melted at 180°C-200°C for at least 20 minutes and an approximately 1 / 4" wide bead of adhesive was poured onto the kraft paper in the template opening. A second sheet of kraft paper was placed on top of the adhesive with the inside surface facing down. A 4.5lb hand roller was passed over the bond line twice. The bonded kraft paper was cut into 1" wide strips and the strips were conditioned in a constant temperature and humidity (CTH) chamber for 24 hours prior to testing. Standard CTH conditions are 70°F + / - 3°F (21°C + / - 2°C) and 50% (+ / - 5%) relative humidity.

[0345] The substrate was 40 lb virgin kraft paper. The adhesive thickness was approximately 15-20 mils and the bond area was 1" x 1". A static load of 500 g was used in a programmable oven equipped with a Cheminstruments 30 group tester according to ASTM D4498 with a heating rate of 0.5°C / min.

[0346] 3.180 degree peel strength

[0347] The 180 degree peel strength of laminates PP / TPO or ABS / TPO (TPO-1 or TPO-2) was measured on an MTS Criterion 43 Electromechanical Universal Test System at a speed of 300 mm / min. The bonds were aged for at least 24 hours before determining the peel strength. The substrate size was 4" x 1". After each measurement, the peeled specimens were observed and their failure modes were recorded, which included cohesive failure (Coh), adhesive failure (Adh), a combination of adhesive failure and cohesive failure (A+C), adhesion failure to foil (AFF), adhesion failure to substrate (AFS), and TPO foil failure (FF).

[0348] When testing 180 degree peel strength at 90° C. or 120° C., the aged samples were pulled off using the MTS tester located in a thermal chamber with the corresponding temperature. The samples stayed in the chamber for 5 minutes before measurement.

[0349] 4. Thermal creep test

[0350] 4.1 Laminate of PP and TPO-2

[0351] The lamination of PP and TPO-2 is the same as the 180 degree peel strength, where the bond length is about 2 inches (50mm). After bonding, the laminate PP / TPO-2 with dimensions of 4"×1" and a bond area of ​​2"×1" at one end of the PP is kept at room temperature for 24 hours or more. A 100 gram weight is then attached to the TPO foil so that when the laminate is tested, the TPO and the substrate PP are at an angle of 90°. The laminate is placed in an oven at a preset temperature for 24 hours. After 24 hours, the distance that the TPO is peeled from the PP is measured and recorded as the creep length. The samples are tested in triplicate and if the average creep length is no greater than 5mm, it means that the test has passed.

[0352] 4.2 Laminates of plywood and MDF

[0353] Adhesive films were prepared using a 6" x 6" PET frame with a thickness of 5 mils under a Carver sheeter with 0 psi pressure applied and held at 193°C for 1.5 minutes. After cooling, the adhesive film was cut into 1" x 4" strips and placed on a 2" x 6" MDF board. A 1" x 4.5" piece of Tecofoil TM The tape was placed on top of the adhesive tape and the metal plate was placed on top of the Tecofoil. The assembled sample was placed in a Carver sheet press and pressed at 193°C with 0 psi until the adhesive tape melted and the MDF and Tecofoil were laminated together.

[0354] After the sample has rested for 24 hours, it is secured in a test stand and a 10 gram or 40 gram weight is attached to the Tecofoil tail to form a 90 degree angle between the MDF and the Tecofoil tail / weight. The test assembly is then placed in an oven at the desired starting temperature. The oven temperature is increased by 10°C per hour. When the Tecofoil delamination distance from the MDF reaches 7 cm, the temperature is recorded as the sample failure temperature. The samples are tested in triplicate and the average failure temperature is reported.

[0355] 5. Static load test

[0356] Static load test specimens were prepared according to General Motor Specification GM 9986384 (purchased specification). Two polypropylene (PP-1) cubes with dimensions of 1" x 1" x 1" and a small hole in the middle were bonded together by applying adhesive on one of the cubes and then mating with the other cube. A 1 Kg weight was placed on top of the bonded blocks until they reached room temperature. A total of 3 specimens with adhesive thickness of 0.5 mm to 0.7 mm were prepared.

[0357] The specimens were hung on the shelf of an oven with a weight attached. The weights were predetermined to be 200 g, 300 g or 500 g, while the oven temperature was selected to be 110° C., 120° C. or 130° C. If no bond failure occurred after 24 hours, the test was recorded as passed.

[0358] 6. Weather resistance test or weather suitability test

[0359] The weatherability test was selected according to BMW PR308.2 "Climatic test for bonded joints and composite materials on trim parts". The test was conducted in an Espec BTX-475 temperature and humidity chamber (ESPEC North America, Inc. (Hudsonville, MI, USA)). The test was 20 cycles, and the duration of one cycle was 12 hours. Each test cycle consisted of the following sequence: (a) heating from 23°C at 20% relative humidity (RH) for 1 hour; (b) keeping at 90°C and 80% RH for 4 hours; (c) cooling and dehumidifying for 1 hour; (d) keeping at 23°C and 20% RH for 1 hour; (e) keeping at -30°C for 4 hours; (f) heating to 23°C at 20% RH within 1 hour.

[0360] 7. Lap shear strength test

[0361] The bonding procedure was as described above for SAFT birch wood lamination, except that the substrate dimensions were 4" x 1" and the bonding area was 1" x 0.5". Strength was measured on an MTS Criterion Model 43 Electromechanical Universal Testing System at a speed of 12.7 mm / min. A minimum of five specimens were tested for each sample and the average value reported.

[0362] 8. Packaging cardboard fiber tearing test

[0363] Prepare samples for adhesion testing by applying a 350°F (177°C) adhesive bead to the bonding surface of the corrugated cardboard and immediately in close contact with the inner surface of a piece of corrugated cardboard; the cardboard flutes of both substrates are vertical. Condition the samples at room temperature for a minimum of 4 hours before testing, or condition the samples at room temperature overnight and then at 60°C for 4 hours ± 0.5 minutes to standardize any migration of components that may affect adhesion performance. Separate the bonded cardboard substrates by hand at room temperature or immediately after removal from the conditioning oven. Visually inspect the substrates and estimate the fiber tear percentage to the nearest 5%. Test at least three samples.

[0364] Table 5 lists the inventive propylene-ethylene copolymers used in the inventive compositions formulated for application performance testing, including the convenient class names of the inventive copolymers from Tables 1A and 1B: (1) high viscosity, high elongation and high RBSP polymers, (2) medium viscosity, high elongation and high RBSP polymers, (3) ultra-high viscosity and high RBSP polymers, and (4) low viscosity and high RBSP polymers. Table 6 lists the properties of the comparative polyolefin polymers tested, where the corresponding polymer class name is based solely on the viscosity of the commercially available comparative polymer tested.

[0365] The propylene-ethylene copolymers of the present invention in category 1 are preferably used in sanitary adhesives; the propylene-ethylene copolymers in categories 2 and 3 are preferably used in laminating, woodworking and edge banding adhesives. It is particularly noteworthy that the propylene-ethylene copolymers of the present invention in category 4, Examples 22, 23 and 24, which have relatively low viscosities (3,000 cp to 6,000 cp) and high RBSP, are surprisingly useful in packaging adhesives. Table 5C also shows three commercial polyolefin polymers used as comparative examples.

[0366] Table 5

[0367]

[0368]

[0369] Table 6 - Properties of Commercially Available Comparative Polymer Examples

[0370]

[0371] Inventive Examples 24-43 and Comparative Examples 10-12: Comparison of polymers with standard compositions

[0372] All examples were prepared as previously described in the experimental section under "Preparation of Hot Melt Adhesives". Example compositions are given as weight percent (wt%) based on total composition weight. The amount of antioxidant added is based on the total weight of the other ingredients.

[0373] Table 7A, Table 7B and Table 7C give the properties of the inventive propylene-ethylene copolymers and comparative polymers having a typical formulation containing 70 wt% polymer and the same type and amount of tackifier resin, wax and antioxidant. Except for inventive Examples 3 and 4 containing lower elongation polymers, the inventive examples exhibit high softening points of 142°C to 151°C, high tensile strengths in the range of 3MPa to 7MPa and high elongations (450%-780%).

[0374] The hot melt adhesive compositions of Examples 24 to 43 of the present invention exhibited strong 180 degree peel strength tested at 25° C., indicating sufficient adhesion to bond polypropylene and TPO-1, substrates frequently used in automotive components. The shear adhesion failure temperature (SAFT) as measured by ASTM D4498 was surprisingly 124° C. or higher compared to Comparative Examples 7 or 8 (116° C. and 95° C.), indicating that the polymers and adhesive compositions of the present invention have sufficient heat resistance at high temperatures for use in automotive interior parts and other applications requiring improved heat resistance.

[0375] Inventive Examples 25-43 were prepared using inventive polymers from class (1) and can be compared to Comparative Example 10, which was prepared using a commercially available polymer in the same viscosity range.

[0376] The inventive examples comprise polymers having Ring and Ball softening points of 138°C to 158°C, and surprisingly, the formulated compositions have RBSPs of 142°C to 151°C, and their RBSPs are reduced by 7°C or less compared to the starting polymer. In contrast, Comparative Example 10, which comprises a polymer having an RBSP of 161°C, results in a formulated composition having an RBSP of 150°C, and its RBSP is reduced by 11°C. Comparing Inventive Examples 25-43 with Comparative Example 10 reveals that the RBSP of the compositions can be maintained, thereby allowing the inventive examples to be used in place of the comparative examples when the RBSP of the product is specified, while also allowing improvements in the properties of the compositions as discussed below.

[0377] Inventive Examples 25-43, while maintaining RBSP similar to Comparative Example 10, also surprisingly have viscosities of about 6800 cP to about 12500 cP at 190°C that are up to 57% lower than Comparative Example 10, allowing for the possibility of better processing, lower addition or lower application temperatures, and other commercial benefits. Surprisingly, Inventive Examples 25-43 all have SAFT values ​​that are about 9% to about 28% greater than Comparative Example 10, as measured using PP-PP as previously described, with SAFT values ​​ranging from about 125°C to about 150°C.

[0378] The inventive examples maintain or have greater 180 degree peel strength between PP and TPO-1 foil substrates at 25° C., with inventive example 43 having a peel strength surprisingly greater than 91% of that of comparative example 10, with peel values ​​up to about 80 N / 25 mm at 25° C. under the specified substrate and test conditions. Unexpectedly, the inventive examples have peel strength greater than comparative example 10 by as much as 188% (inventive example 40), with peel values ​​up to about 5 N / 25 mm at 90° C.

[0379] Inventive Examples 25-43 also have elongation values ​​that are about 42% to about 250% greater than the comparative examples; some of the inventive examples also have comparable elongation at break, where the values ​​are less than 20% lower than the elongation at break of the comparative examples.

[0380] Inventive Examples 32, 35, 37 and 38 were prepared using inventive polymers from class (2) and can be compared to Comparative Examples 11 and 12, each prepared using a commercially available polymer in the same viscosity range.

[0381] For category (2), there was no difference in the change of RBSP from polymer to formulated composition.

[0382] Compared to Comparative Example 11, Inventive Examples 32, 35, 37, and 38 have surprisingly high RBSP of 26% to 30%, elongation at break of about 255% to about 400%, and about 30% to about 45%. Inventive Examples 35, 37, and 38 surprisingly also have about 69% to about 26% higher 180 degree peel strength at 90°C, PP / TPO-1, indicating improved performance in high heat environments. In addition, compared to Comparative Example 11, Inventive Examples 32, 35, 37, and 38 have surprisingly high RBSP of 26% to 30%, elongation at break of about 255% to about 400%, and about 30% to about 45%. Inventive Examples 35, 37, and 38 surprisingly also have about 69% to about 26% higher 180 degree peel

[0383] Compared to 11, inventive examples 35, 37 and 38 also unexpectedly and simultaneously maintain comparable viscosity at 190°C and comparable 180 degree peel strength at 25°C for PP / TPO-1.

[0384] Inventive Examples 35, 37, and 38 have similar viscosities but unexpectedly have about 25% to about 50% higher tensile values ​​than Comparative Example 12. Inventive Examples 37 and 38 also have 35% to 84% higher 180 degree peel strength at 90°C, PP / TPO-1 than Comparative Example 12, indicating improved performance in high heat environments.

[0385]

[0386]

[0387]

[0388] 2. High heat resistance

[0389] Selected previously prepared compositions are shown in Table 8, and their viscosities at 190°C range from 9000 cp to 16000 cp and about 4000 cp. The open times of the examples of the present invention are in excess of 40 seconds, which is an acceptable working time for many assembly, automotive, and woodworking applications. These open times can be further optimized by those skilled in the art, and the effects of varying the wax used in the composition are explained later in this disclosure.

[0390] In addition to forming an acceptable initial bond, it is also desirable to maintain the bond after exposure to the external environment, as simulated by tests known in the art, such as weatherability tests or weatherability tests. The results in Table 8 are discussed below and show surprising retention of SAFT and peel strength of laminates PP / PTO-1 and ABS / TPO-1 for the compositions of the present invention after weatherability testing.

[0391] Inventive Examples 25, 36, 38, 40, and 41 were prepared using inventive polymers from class (1) and are comparable to Comparative Example 10 prepared using polymers in the same viscosity range. All of the inventive examples had PP / PP SAFT temperatures that were about 20%-25% higher than Comparative Example 10. The about 51%-86% higher PP / TPO-1 180 degree peel strength at 25°C and about 31% higher ABS / TPO-1 180 degree peel strength at 25°C compared to Comparative Example 10 showed superior heat resistance retention after weathering testing.

[0392] Typically, all examples have lower SAFT and peel values ​​after the weathering / weathering test cycle; however, after the weathering test, Inventive Example 36 unexpectedly has about 27% higher PP / PP SAFT temperature at 25°C and about 27% higher PP / TPO-1 180 degree peel strength. Inventive Examples 25, 36, 38, and 41 also unexpectedly have about 18%-36% higher ABS / TPO-1 180 degree peel strength at 25°C than Comparative Example 10, showing superior heat resistance property retention after weathering testing.

[0393] Inventive Examples 37 and 39 were prepared using inventive polymers from class (2) and are comparable to Comparative Examples 11 and 12. The formulated viscosities were comparable. Inventive Examples 37 and 39 had SAFT PP / PP values ​​that were about 45% higher than Comparative Example 11. As with the examples from polymer class (1), all examples had lower SAFT and peel values ​​after the weathering / weathering test cycles; Comparative Example 11 lost about 86% of its PP / TPO-1 and ABS / TPO-1 180 degree peel strength at 25°C. Inventive Examples 37 and 39 and Comparative Example 12 all retained acceptable PP / TPO-1 and ABS / TPO-1 180 degree peel strengths at 25°C after weathering / weathering exposure. Although Comparative Example 12 had a higher starting SAFT PP / PP value, Inventive Example 39 unexpectedly had a higher SAFT PP / PP (about 5% higher) than Comparative Example 12 after weathering testing.

[0394]

[0395] Tables 9A and 9B show the peel strength PP / TPO-2 measured at temperatures from 25°C to 120°C. The peel strengths of the inventive examples and comparative examples at 25°C are similar because the bonding on the TPO-2 exhibits foil failure (also known as foam layer failure, FF) during the peeling process. At higher temperatures of 90°C and 120°C, most of the inventive example adhesives exhibit surprisingly higher peel strengths than the comparative examples, indicating that the inventive examples retain strong cohesive strength behavior and high heat resistance. Compared to Comparative Example 10, category (1) inventive examples 25, 36, 38, 40 and 41 have peel values ​​that are about 109% to about 365% higher at 90°C and about 220% to about 595% higher at 120°C. Most surprisingly and advantageously, inventive example 38 has a foil failure at 120°C compared to the cohesive failure of the adhesive in Comparative Example 10, indicating that the inventive example 38 adhesive has even stronger strength than the TPO foil at this temperature.

[0396] After exposure to weathering in the weatherability test, the 180 degree peel strength at 90°C, PP / TPO-2 for Inventive Examples 38, 40 and 41 unexpectedly and advantageously exhibited foil failure compared to the cohesive failure of the adhesive in Comparative Examples 10 and 12 and the commercial adhesive Comparative Example 14. This resulted in peel strength values ​​that were about 575% to about 660% higher than Comparative Example 10.

[0397] After exposure to weathering in the weatherability test, the 180 degree peel strength at 120°C, PP / TPO-2 of Inventive Example 38 most unexpectedly and advantageously exhibited foil failure compared to the cohesive failure of the adhesive in Comparative Example 10, with a peel strength value of about 475% higher than that of Comparative Example 10. Inventive Examples 40 and 41, as well as Comparative Examples 10, 13, and Commercial Adhesive Comparative Example 13 all exhibited cohesive failure; however, the 180 degree peel strength at 120°C, PP / TPO-2 of Inventive Examples 40 and 41 was about 178% to about 211% greater than the peel value of Comparative Example 10, indicating that all of the Inventive Examples tested had superior heat resistance and cohesion. Unexpectedly, the 180 degree peel strength at 120°C, PP / TPO-2 of Inventive Example 40 was about 84% and about 57% higher than that of the commercial adhesives tested as Comparative Examples 13 and 14. The inventors found this to be particularly surprising since the formulations of the inventive examples were not optimized, whereas the commercial adhesives were optimized.

[0398]

[0399]

[0400] The measurement of thermal creep is a critical test for automotive components, and reactive cross-linking adhesives are used when heat resistance of 120° C. is required. Tables 10A and 10B show the unexpected result that the heat resistant copolymers and hot melt compositions of the present invention can provide thermal creep resistance at 120° C. without cross-linking.

[0401] The heat resistance measured by the hot creep test and the static load test are listed in Table 10A and Table 10B. For the hot creep test, the laminate was placed in an oven at a preset temperature for 24 hours. If the average TPO peel distance (creep length) from PP is not greater than 5 mm (less than or equal to 5 mm), it means that the test is passed. The tested embodiments of the present invention containing polymers from categories (1) and (2) all passed the hot creep test at 90°C, while all comparative embodiments containing polymers from categories (1) and (2) did not pass the hot creep test at 90°C. Both commercial adhesives, Comparative Example 13 and Comparative Example 14, passed the hot creep test at 90°C.

[0402] Both commercial adhesives, Comparative Example 13 and Comparative Example 14, failed the thermal creep test at 100°C; however, unexpectedly, inventive examples 25, 36, 38, 40 and 41 passed the thermal creep test at 100°C; inventive examples 25, 38, 40 and 41 passed the thermal creep test at 110°C, and most surprisingly, inventive examples 25, 38 and 40 passed the thermal creep test at 120°C. Passing the thermal creep test at 120°C indicates "the possibility of greatly improving heat resistance" because it can be used to replace cross-linked reactive adhesives. Some inventive example adhesive compositions pass thermal creep temperatures as high as 110°C or even 120°C, indicating strong resistance to higher temperatures. Unexpectedly, a positive correlation was observed between the adhesive thermal creep failure temperature and the peel strength at that temperature. This means that the greater the peel strength at the test temperature, the higher the possibility of passing the thermal creep test at the same temperature.

[0403] For the static load test, Inventive Examples 25, 36, 38, 40 and 41 (Class 1 polymers), Inventive Examples 37 and 39 (Class 2 polymers), and Comparative Example 12 passed the test using a 200 g weight at 110° C. Comparative Examples 10 and 11 both failed the static load test using a 200 g weight at 110° C.

[0404] Inventive Examples 36, 38, 40 and 41 (Class 1 polymers), Inventive Examples 37 and 39 (Class 2 polymers) unexpectedly withstood the 1-day static load test using a 300 g weight at 130° C. Surprisingly, Inventive Examples 36 and 40 passed the test using a 500 g weight at 110° C., and the inventors were most surprised to find that Inventive Example 41 even passed the test using 500 g at 120° C., again demonstrating the excellent heat resistance properties of compositions comprising the previously disclosed inventive polymers.

[0405]

[0406]

[0407] 3. Recipe variables

[0408] 3.1 Tackifier resin

[0409] The example adhesives of the present invention having the same copolymer but different tackifier resins were evaluated and the results are shown in Table 11. The ingredients listed are provided in weight percentage based on the total weight of the adhesive. The amount of antioxidant added is based on the total weight of the other ingredients. All adhesives showed strong peel strength even at higher temperatures, indicating that the copolymers of the present invention have very good compatibility with a wide range of hydrogenated C5, hydrogenated PMR and hydrogenated C8 / C9 tackifier resins.

[0410] Table 11

[0411]

[0412] FF = foil failure (in the foam layer); coh = cohesive failure of the adhesive composition; adh = adhesive failure of the adhesive composition

[0413] 3.2 Wax and acid-modified tackifier resins

[0414] In Table 12, inventive adhesives with the same copolymer and tackifier resin but with different waxes were evaluated. The waxes included polypropylene (PP) waxes with maleic anhydride grafted functional groups (inventive examples 44, 49-52) and PP waxes without any functional groups (inventive examples 53 and 54). The viscosity of the waxes at 190°C ranged from 150 cp to 18,000 cp and 60,000 cp. Due to the low wax ratio in the formulation, except for inventive example 50 (wherein the maleic anhydride-modified PP wax Eastman TM The different waxes seemed to change little about the properties of the adhesive, except that G3003 had a very high viscosity and provided higher RBSP and stronger peel strength at 120°C.

[0415] Inventive Examples 53 and 54 contain unfunctionalized / maleated wax. The effect of the lower softening point of the wax is seen in the lower SAFT of the composition. Surprisingly, despite the lower softening point of the wax used, Inventive Example 54 maintained partial foil failure at 90°C, demonstrating how the heat resistance of the inventive polymer in the composition maintains tensile strength, elongation at break, and 180 degree peel strength at 25°C and 90°C. Changing the wax type allows the formulator to adjust the open time (40 seconds - 70 seconds), needle penetration or hardness (3.5 dmm to 4.2 dmm), adhesive RBSP (138°C - 152°C), adhesive SAFT (135°C - 148°C), and adhesive viscosity (8300 cP - 11000 cP at 190°C) to balance adhesive properties as desired. These examples are simple illustrations of using one additive level without changing the other components, and one skilled in the art will be able to build on this knowledge.

[0416]

[0417] In Table 13, the functionalized wax Epolene E43 in the adhesive formulation was replaced by dimerized and partially dimerized rosin acid tackifier resins. Rosin acid is compatible in the inventive copolymer formulations, and inventive Example 56 with partially dimerized rosin acid unexpectedly passed the hot creep test at 100° C. Based on the hot creep test, dimerized rosin acid does not show improvement in adhesive adhesion at higher temperatures compared to maleic anhydride grafted polypropylene wax.

[0418] Table 13

[0419]

[0420] The effect of the amount of wax on the adhesive properties and performance of the compositions is shown in Table 14. The ratio of the inventive copolymer to the tackifier resin was kept constant in all formulations (70:25). TM The amount of Epolene E43 was increased from 0 to 30 wt% (inventive examples 57-60), the amount of Epolene E43 was kept at 5 wt%, and the amount of Epolene N15 using a second unmodified PP wax was increased from 5 wt% to 15 wt% (inventive examples 61 and 62).

[0421] Surprisingly, it was found that Inventive Example 57, which contained no wax, maintained PP / TPO-2 180 degree peel strength at 90°C and experienced substrate foil failure / cohesive failure, as well as passing the hot creep test at 110°C. Up to 20 wt% maleated PP wax improved performance and reduced open time, with 30 wt% maleated PP wax reducing elongation. The combination of 5 wt% maleated PP wax and 15 wt% PP wax (Inventive Example 62) demonstrates the formulation flexibility of the inventive copolymers, allowing similar adjustments in adhesive open time and viscosity while tolerating lower elongation. Higher amounts of wax in the formulation reduced open time due to crystallization of the PP wax during cooling of the molten adhesive. Increased wax levels also resulted in decreased viscosity and tensile elongation, while increasing softening point and SAFT.

[0422] Table 14

[0423]

[0424] 3.3 Ratio of the copolymer of the present invention to the tackifier resin

[0425] In Table 15A, Table 15B and Table 16, the ratio of tackifier resin to inventive copolymer varied between values ​​of about 0:1, about 0.06:1, about 0.2:1, about 0.3:1, about 0.4:1, about 0.5:1, about 0.6:1 and about 0.9:1. Surprisingly, all of the inventive compositions having a ratio of tackifier resin to inventive copolymer below 0.6:1 maintained a RBSP of about 140°C or higher and passed the hot creep test at 110°C, PP / TPO-2. The inventors were surprised to find that inventive Examples 38 and 64 passed the hot creep test at 120°C, PP / TPO-2, which is typically only passed by crosslinked adhesives. Most unexpectedly, inventive Example 64 passed both the hot creep test at 120°C, PP / TPO-2 and the 1-day static load test at 110°C, PP-1 / PP-1 using 500g.

[0426] Table 15A

[0427]

[0428] Table 15B

[0429]

[0430]

[0431] NT = Not Tested; FF = Foil Failure (in Foam Layer); Coh = Cohesive Failure of Adhesive Composition

[0432] It is also noted that the lower the ratio of tackifier resin to the inventive copolymer in the formulation, the higher the temperature passed in the thermal creep test, corresponding to increased peel strength at higher temperatures. This correlation provides the formulator with the opportunity to balance the heat resistance and peel strength of the composition by varying the amount of tackifier or eliminating the use of tackifier resin.

[0433] Table 16

[0434]

[0435]

[0436] FF = foil failure (in foam layer); coh = cohesive failure of adhesive composition; adh = adhesive failure of adhesive composition; NT = not tested

[0437] 3.4 Blends with other polymers

[0438] Table 17, table 18 and table 19 show the present composition of the present invention that heat-resistant propylene-ethylene copolymer of the present invention is blended with styrene block copolymer, amorphous polyolefin polymer or metallocene catalyzed alpha-polyolefin polymer.The listed ingredients are provided with the weight percentage based on the total weight of adhesive.The amount of added antioxidant is based on the gross weight of other ingredients.These embodiments illustrate that these kinds of polymers can be blended with copolymer of the present invention and keep heat resistance and obtain favorable characteristic balance.Those skilled in the art can use these preparations as the starting point for further preparation.

[0439] In the example adhesives shown in Table 17, inventive copolymer Example 18 was blended with Kraton G1643 (a commercial triblock copolymer based on styrene and ethylene / butylene) at SEBS:inventive copolymer ratios of about 0.09: 1, about 0.14: 1, and about 0.17: 1. Inventive copolymer and SEBS blend Inventive Example 40 had foil failure at 90°C PP / TPO-2 180 degree peel strength, passed the 120°C PP / TPO-1 hot creep test, and passed the 1 day static load test at 110°C, PP-1 / PP-1 and using 500g, demonstrating surprising heat resistance retention of the inventive copolymer in the composition.

[0440] The presence of SEBS polymer in a formulation with a tackifier resin and wax generally reduces the 120° C. heat resistance of the inventive composition, as shown by cohesive failure in the 180 degree peel strength test at 120° C. and failure in the hot creep test at 120° C., PP / TPO-1. The inclusion of Epolene N-15 wax in the inventive composition with both polymer and wax generally improves the peel performance.

[0441] Table 17

[0442]

[0443]

[0444] FF = foil failure (in foam layer); coh = cohesive failure of adhesive composition; adh = adhesive failure of adhesive composition; NT = not tested

[0445] In the inventive examples of Table 18, the heat resistant copolymer inventive example 18 was blended with the commercial polymer comparative example 7 in different ratios and with or without additional wax. Unexpectedly, it was found that the addition of comparative example 7 to the inventive copolymer reduced the heat resistance of the adhesive composition. However, the results can be read the other way around, i.e., the inventive copolymer unexpectedly improved the heat resistance of the composition based on the comparative example 7 polymer. The additional Epolene N15 wax appears to improve the hot creep properties, but reduces the static load properties.

[0446] Table 18

[0447]

[0448]

[0449] FF = foil failure (in foam layer); coh = cohesive failure of adhesive composition; adh = adhesive failure of adhesive composition; NT = not tested

[0450] In the inventive example adhesives shown in Table 19, the inventive example 18 copolymer is blended with a commercially available copolymer produced by a Ziegler-Natta catalyst (in inventive example 82) or with a commercially available polyolefin copolymer produced with a metallocene catalyst (in inventive example 83). The inventive adhesives not only exhibit excellent tensile strength and elongation, but also exhibit a high SAFT of 22% greater than that of comparative example 10, and a 180 degree peel strength at 25°C, PP / TPO-1 of about 5% to about 66% greater than that of comparative example 10, and a 180 degree peel strength at 90°C, PP / TPO-1 of about 69% to about 190% greater than that of comparative example 10. The high SAFT and the higher peel strength at 90°C illustrate the surprising heat resistance of the formulations containing the new propylene-ethylene copolymers. The inventors note that inventive examples 40, 69 and 70 also surprisingly have tensile strengths of about 150% to about 260% greater than that of comparative example 10.

[0451] Table 19

[0452]

[0453]

[0454] 4. Woodworking application

[0455] Woodworking applications include profile packaging, lamination, and other wood assembly using plywood, paper, foil, and plastic. Adhesives need to have low odor, as well as higher heat resistance and greater cohesive strength than is typically available with current commercial polyolefin polymers. The present propylene-ethylene heat resistant copolymers address this need in the formulation of woodworking adhesives.

[0456] Tables 20A and 20B compare the heat resistance (as measured by SAFT and 90 degree creep tests) and lap shear strength of selected inventive examples comprising the inventive copolymer and Comparative Example 10.

[0457] Compared to Comparative Example 10, Inventive Examples 33, 36, 37, 38, and 41 all unexpectedly have about 30% higher SAFT, about 8% to about 20% higher 90 degree creep failure temperature for assembling MDF board and Tecofoil V paper, and about 80% to about 230% higher lap shear strength, measured as specified in the table.

[0458] Table 20A

[0459]

[0460]

[0461] Table 20B

[0462]

[0463] 5. Packaging application

[0464] The present invention embodiment 8,22 and 23 in the heat-resistant copolymer category (4) of the present invention with a viscosity of 3,000cp to 6,000cp at 190°C and a RBSP exceeding 140°C are surprisingly very suitable for packaging adhesives, and solve the need for adhesives with tolerance to the high temperatures experienced by boxes, cartons and packaging when stored in a warehouse that is not temperature-controlled (especially when the pallet of the product is piled high). Such adhesives can be used for boxes, boxes, sealed cartons and other applications requiring heat resistance. Exemplary formulations are shown in Table 21A, Table 21B and Table 21C, which include low-viscosity heat-resistant propylene-ethylene copolymers, tackifiers and a mixture of PE wax, PP wax and functionalized PP wax. The formulation changes between 37% to 76% polymer, 5% to 35% tackifier resin and 10% to about 33% total wax, resulting in a viscosity of the formulated adhesive at 180°C in the range of about 415cP to about 4000cP. The additional content of maleated PP wax is 2% or 5%, based on the total weight of the formulation. The choice of wax and the ratio of PE wax, PP wax and maleated PP wax used can be varied by one skilled in the art to adjust the balance of viscosity, RBSP, SAFT, adhesion and other properties of the formulated adhesive. According to the technical data sheet, Baker-Hughes Polywax 850 (PE wax) has a melting point of 107°C and a viscosity of 10 cP at 150°C, and according to the technical data sheet, Honeywell MAPP AC-596 maleic anhydride copolymer has a Mettler dropping point (ASTM D-3954) of 141°C and a viscosity of 150 cP at 10°C. The examples given do not cover all properties, but indicate a wide range of properties that can be obtained while maintaining heat resistance, as demonstrated by the fiber tearing performance at 60°C.

[0465] Inventive Examples 84, 89, and 96 have a polymer / tackifier / wax weight ratio of about 75 / 15 / 10 by weight, and a surprisingly desirable combination of viscosity, room temperature fiber tear on corrugated cardboard, 60°C fiber tear on corrugated cardboard, and shear adhesion failure temperature range for packaging applications. This composition also contributes to the best fiber tear percentage tested at both room temperature and 60°C, and exhibits excellent heat resistance based on SAFT (132°C to 134°C).

[0466] Surprisingly, inventive Example 89, with almost 17% total wax content, has excellent fiber tear and a SAFT of 134°C at both room temperature (93%) and 60°C (97%); the overall formulation is 70 / 30 / 17 polymer / tackifier / wax.

[0467] Unexpectedly, Examples 93 and 95 of the present invention, formulated 50 / 27 / 23, have excellent 60°C fiber tear (92%-98%) and acceptable room temperature fiber tear (55%-65%) while having very low viscosities (657 cP-675 cP at 180°C), which is highly desirable for high speed packaging lines.

[0468] Table 21A

[0469]

[0470]

[0471] Table 21B

[0472]

[0473] Table 21C - Performance properties of adhesive compositions comprising copolymers of the present invention produced with Generation 5 / 6 catalysts.

[0474] Element Embodiment 126 of the present invention Embodiment 107 of the present invention 76 <![CDATA[Regalite TM R1125]]> 14 <![CDATA[Polywax TM 850, PE wax]]> 6 <![CDATA[Licocene TM PP 6102, PP 6102]]> 2 <![CDATA[AC TM -596, maleated PP wax]]> 2 <![CDATA[Irganox TM 1010]]> 0.2 Formulation properties and performance Room temperature flexibility Flexibility Molten appearance clarify Viscosity at 180°C, cP 2,070 RBSP,℃(ASTM E-28) 138.5 Room temperature fiber tearing (%, average of 3 times) 100 Fiber tearing at 60℃ (%, average of 3 times) 95 PAFT, °C, ASTM, Kraft paper, 100g 38 SAFT, °C, ASTM, Kraft paper, 500g 133

[0475] definition

[0476] It should be understood that the following is not intended to be an exclusive list of defined terms. Other definitions may be provided in the foregoing description, for example, when contextually accompanying the use of a defined term.

[0477] As used herein, the terms "a," "an," and "the" mean one or more.

[0478] As used herein, the term "about" refers to any value within the range of 90% to 110% of the specified value. However, it should be noted that all values ​​associated with "about" include support for the specific value itself and the range associated with the "about" specific value. For example, "about 10" provides support for the specific value "10" and the range from 9 to 11. In addition, the term "about" can be associated with any specific value described herein.

[0479] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as comprising components A, B, and / or C, the composition may comprise only: A alone; B alone; C alone; a combination of A and B; a combination of A and C, a combination of B and C; or a combination of A, B, and C.

[0480] As used herein, the term "comprising" is an open transition term used to transition from subject matter referenced before the term to one or more elements referenced after the term, where the one or more elements listed after the transition term are not necessarily the only elements making up the subject matter.

[0481] As used herein, the term "having" has the same open-ended meaning as "including" provided above.

[0482] As used herein, the term "comprising" has the same open-ended meaning as "including" provided above.

[0483] This specification uses numerical ranges to quantify certain parameters associated with the present invention. It should be understood that when a numerical range is provided, such range should be interpreted as providing textual support for claim limitations that only record the lower limit of the range and claim limitations that only record the upper limit of the range. For example, a public numerical range of 10 to 100 provides textual support for a claim stating "greater than 10" (no upper limit) and a claim stating "less than 100" (no lower limit).

[0484] When indicating a numerical sequence, it should be understood that each number is modified to be the same as the first or last number in the numerical sequence or in the sentence. For example, if each number is stated as "at least" or "not more than", each number is in an "or" relationship. In an exemplary case, "at least 10 weight %, 20 weight %, 30 weight %, 40 weight %, 50 weight %, 75 weight %" means the same as "at least 10 weight % or at least 20 weight % or at least 30 weight % or at least 40 weight % or at least 50 weight % or at least 75 weight %".

[0485] The preferred forms of the present invention described above are for illustration only and should not be used to interpret the scope of the present invention in a limiting sense. Modifications to the above exemplary embodiments may be easily made by those skilled in the art without departing from the spirit of the present invention.

[0486] The inventors hereby declare their intention to rely on the Doctrine of Equivalents to determine and assess the fair and equitable scope of the present invention as it relates to any devices that do not materially depart from but fall outside the literal scope of the present invention as set forth in the following claims.

Claims

1. A propylene-ethylene copolymer, comprising propylene and ethylene; wherein The propylene-ethylene copolymer: (a) contains from 89 to 98% by weight of propylene, (b) having a Ring and Ball softening point of at least 135°C, (c) having a triad tacticity (mm%) of at least 50%, and (d) having a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g.

2. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer comprises 0.5 wt% to 11 wt% ethylene. 3 . The propylene-ethylene copolymer according to claim 1 , wherein the propylene-ethylene copolymer has a viscosity of about 1,000 cP to about 50,000 cP at 190° C.

4. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) having a viscosity of 2,000 cP to 7,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 1.5 MPa to 8 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

5. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) having a viscosity of 7,000 cP to 15,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 3 MPa to 10 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

6. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) having a viscosity of 15,000 cP to 27,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 3 MPa to 14 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

7. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) having a viscosity at 190°C greater than 27,000 cP, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of at least 7 MPa, and (d) Heat of crystallization of 25 J / g to 50 J / g.

8. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135°C to 160°C.

9. The propylene-ethylene copolymer according to claim 8, wherein the propylene-ethylene copolymer has a triad tacticity in the range of 50% to 70%. 10 . The propylene-ethylene copolymer according to claim 9 , wherein the propylene-ethylene copolymer has a needle penetration force in the range of 0.1 dmm to 21 dmm.

11. The propylene-ethylene copolymer of claim 10, wherein the propylene-ethylene copolymer exhibits a tensile strength at break ranging from 1.5 MPa to 14 MPa.

12. The propylene-ethylene copolymer of claim 11, wherein the propylene-ethylene copolymer has an elongation at break greater than 300%.

13. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer has a heat of crystallization (Hc, 20°C / min cooling rate) ranging from 20 J / g to 55 J / g.

14. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) exhibits needle penetration ranging from 0.1 dmm to 21 dmm, (b) has a heat of crystallization of 25 J / g to 55 J / g, and (c) Having one of the following characteristics: (i) having a viscosity of 2,000 cP to 7,000 cP at 190°C and exhibiting a tensile strength at break of 1.5 MPa to 8 MPa, or (ii) having a viscosity of 7,000 cP to 15,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 8 MPa, (iii) having a viscosity of 15,000 cP to 27,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 14 MPa, or (iv) having a viscosity greater than 27,000 cP at 190°C, exhibiting a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 J / g to 50 J / g.

15. The propylene-ethylene copolymer according to any one of claims 1 to 3, wherein the propylene-ethylene copolymer: (a) having a triad tacticity in the range of 53% to 78%, (b) exhibit a Ring and Ball softening point of 135°C to 165°C, and (d) exhibits a heat of crystallization of 28 J / g to 60 J / g.

16. The propylene-ethylene copolymer according to any one of claims 1 to 3 or 15, wherein the propylene-ethylene copolymer: (a) having a viscosity of 15,000 cP to 50,000 cP at 190°C, (b) exhibit a tensile strength at break of at least 3 MPa, and (c) exhibit an elongation at break of at least 300%.

17. A composition comprising the propylene-ethylene copolymer according to claim 1.

18. A process for producing the propylene-ethylene copolymer according to claim 1, wherein the process comprises polymerizing ethylene and propylene in the presence of a Ziegler-Natta catalyst system.

19. An adhesive composition, comprising: (a) 5 to 100 weight percent of at least one propylene-ethylene copolymer, wherein the propylene-ethylene copolymer comprises ethylene and propylene, wherein the propylene-ethylene copolymer: (i) contains from 89 to 98% by weight of propylene, (ii) having a Ring and Ball softening point of at least 135°C, (iii) having a triad tacticity (mm%) of at least 50%, and (iv) having a heat of crystallization (Hc, 20°C / min cooling rate) of at least 25 J / g; (b) 0% to 90% by weight of at least one second polymer; (c) no more than 70% by weight of at least one tackifier; (d) not more than 20% by weight of process oil; and (e) not more than 35% by weight of at least one wax.

20. The adhesive composition of claim 19, wherein the adhesive composition comprises 5 to 55 weight percent of the second polymer.

21. The adhesive composition according to claim 19, wherein the adhesive composition has: (a) a shear adhesion failure temperature of at least 135°C, and / or (b) Thermal creep length of 5 mm or less at 110°C.

22. The adhesive composition according to claim 19, wherein the adhesive composition has: (a) a shear adhesion failure temperature of at least 135°C, and (b) Thermal creep length of 5 mm or less at 120°C.

23. The adhesive composition according to claim 19, wherein the adhesive composition comprises: (a) 10 to 70 wt% of said propylene-ethylene copolymer; (b) 5 to 55 weight percent of the second polymer; (c) no more than 70% by weight of said tackifier; (d) not more than 20% by weight of said process oil; and (e) not more than 20% by weight of said wax.

24. The adhesive composition of claim 19, wherein the adhesive composition comprises: (a) 5 to 95 wt% of said propylene-ethylene copolymer; (b) 5% to 90% by weight of the second polymer; (c) no more than 70% by weight of said tackifier; (d) not more than 20% by weight of said process oil; and (e) not more than 20% by weight of said wax.

25. The adhesive composition of claim 19, wherein the adhesive composition comprises: (a) 30 to 80 wt% of said propylene-ethylene copolymer; (b) 1 wt % to 45 wt % of the second polymer; (c) no more than 70% by weight of said tackifier; (d) not more than 20% by weight of said process oil; and (e) not more than 20% by weight of the at least one wax.

26. The adhesive composition of claim 19, wherein the second polymer is at least one polymer selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers, copolymers produced from propylene and linear or branched C4-C10 alpha-olefin monomers, copolymers produced from ethylene and linear or branched C4-C10 alpha-olefin monomers, Copolymers produced from branched C4-C10 α-olefin monomers, functionalized polyolefins, isoprene-based block copolymers, butadiene-based block copolymers, hydrogenated block copolymers, styrene-ethylene / butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene / propylene-styrene (SEPS), ethylene vinyl acetate copolymers, polyesters, polyester-based copolymers, chloroprene rubber, urethane, acrylic acid, polyacrylate, acrylate copolymers, polyetheretherketone, polyamide, hydrogenated styrene block copolymers, random styrene copolymers, ethylene-propylene rubber, ethylene vinyl acetate copolymers, butyl rubber, styrene-butadiene rubber, nitrile rubber, natural rubber, polyisoprene, polyisobutylene and polyvinyl acetate.

27. The adhesive composition of claim 19, wherein the adhesive composition comprises less than 10 wt% of the wax.

28. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer comprises 0.5 wt% to 11 wt% ethylene.

29. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a viscosity of 1,000 cP to 50,000 cP at 190°C.

30. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a viscosity of 2,000 cP to 7,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 1.5 MPa to 8 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

31. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a viscosity of 7,000 cP to 15,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 3 MPa to 10 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

32. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a viscosity of 15,000 cP to 27,000 cP at 190°C, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of 3 MPa to 14 MPa, and (d) Heat of crystallization of 25 J / g to 55 J / g.

33. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a viscosity at 190°C greater than 27,000 cP, (b) exhibits a needle penetration force of 0.1 dmm to 21 dmm, (c) exhibit a tensile strength at break of at least 7 MPa, and (d) Heat of crystallization of 25 J / g to 50 J / g.

34. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a Ring and Ball softening point in the range of 135°C to 160°C.

35. The adhesive composition of claim 34, wherein the propylene-ethylene copolymer has a triad tacticity in the range of 50% to 70%.

36. The adhesive composition of claim 35, wherein the propylene-ethylene copolymer has a needle penetration force in the range of 0.1 dmm to 21 dmm.

37. The adhesive composition of claim 36, wherein the propylene-ethylene copolymer exhibits a tensile strength at break in the range of 1.5 MPa to 14 MPa.

38. The adhesive composition of claim 37, wherein the propylene-ethylene copolymer has an elongation at break greater than 300%.

39. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer has a heat of crystallization (Hc, 20°C / min cooling rate) in the range of 20 J / g to 55 J / g.

40. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) exhibits needle penetration ranging from 0.1 dmm to 21 dmm, (b) has a heat of crystallization of 25 J / g to 55 J / g, and (c) Having one of the following characteristics: (i) having a viscosity of 2,000 cP to 7,000 cP at 190°C and exhibiting a tensile strength at break of 1.5 MPa to 8 MPa, or (ii) having a viscosity of 7,000 cP to 15,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 8 MPa, (iii) having a viscosity of 15,000 cP to 27,000 cP at 190°C and exhibiting a tensile strength at break of 3 MPa to 14 MPa, or (iv) having a viscosity greater than 27,000 cP at 190°C, exhibiting a tensile strength at break of at least 7 MPa, and a heat of crystallization of 25 J / g to 50 J / g.

41. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a triad tacticity in the range of 53% to 78%, (b) exhibit a Ring and Ball softening point of 135°C to 165°C, and (d) exhibits a heat of crystallization of 28 J / g to 60 J / g.

42. The adhesive composition of claim 19, wherein the propylene-ethylene copolymer: (a) having a viscosity of 15,000 cP to 50,000 cP at 190°C, (b) exhibit a tensile strength at break of at least 3 MPa, and (c) exhibit an elongation at break of at least 300%.

43. An article comprising the adhesive composition of any one of claims 19 to 42, wherein the article is selected from the group consisting of adhesives, sealants, caulks, roofing membranes, waterproofing membranes, compounds and underlayments, carpets, laminates, laminated products, tapes, labels, adhesives, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, modified asphalt, modified asphalt, electronic enclosures, waterproof membranes, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O Rings, motor vehicles, motorcycles, motor vehicle molded parts, motor vehicle extruded parts, clothing articles, rubber additives / processing aids and fibers, wherein the adhesive includes a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile packaging adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible laminating adhesive, a rigid laminating adhesive, a flexible film adhesive, a flexible packaging adhesive, a water-activated adhesive, a home improvement adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a self-adhesive film, a laminating adhesive, a flexible packaging adhesive, a heat sealing adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive or a sanitary elastic attachment adhesive.

Citation Information

Patent Citations

  • Recurrent neural network architecture based classification of atrial fibrillation using single lead ECG

    US11571162B2

  • Adhesive composition

    US20200017731A1

  • Propylene polymer, propylene copolymer, and propylene elastomer prepared using novel bridged indenyl containing metallocenes

    US5504172A

  • Mail-box support.

    US942859A